Positive electrode active material, secondary battery, and method for producing positive electrode active material
By forming a coating of aluminum and magnesium on the surface of the positive electrode active material of the lithium-ion secondary battery, and separating the magnesium oxide on the surface through heat treatment, the capacity reduction and other performance problems of the lithium-ion secondary battery during the cycle are solved, and higher cycle stability and safety are achieved.
Patent Information
- Application Number
- JP2025002459
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2016-11-18
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2037-11-06
AI Technical Summary
The positive electrode active materials of existing lithium-ion secondary batteries still have shortcomings in terms of capacity reduction, charge and discharge characteristics, reliability, safety and cost during the cycle.
A coating of aluminum and magnesium is formed on the surface of the positive electrode active material of the lithium-ion secondary battery. By combining the aluminum and magnesium compounds with lithium ions and transition metal oxides, a composite oxide with a layered rock salt-type crystal structure is formed, and the magnesium oxide is separated on the surface by heat treatment, thereby improving the cycling stability of the battery.
Through this method, the positive electrode active material of lithium-ion secondary batteries can effectively suppress the decline in capacity, improve the charge and discharge characteristics and reliability, enhance the safety of the battery, and reduce production costs.
Smart Images

Figure 2025039702000001_ABST
Abstract
Description
[Technical field]
[0001] One aspect of the present invention relates to an article, a method, or a manufacturing method. Alternatively, the present invention relates to a process, Pertaining to a machine, manufacture, or composition of matter. One embodiment of the present invention is a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, or an electronic In particular, the present invention relates to electronic devices and their operating systems.
[0002] In this specification, the term "electricity storage device" refers to elements and devices having an electricity storage function in general. For example, lithium ion secondary batteries and other storage batteries (also called secondary batteries) These include lithium ion capacitors and electric double layer capacitors.
[0003] In addition, in this specification, the term "electronic device" refers to any device having a power storage device. Electro-optical devices having a power storage device, and information terminal devices having a power storage device are all electronic devices. [Background technology]
[0004] In recent years, various types of storage devices such as lithium-ion secondary batteries, lithium-ion capacitors, and air batteries have become available. The development of lithium-ion secondary batteries, which have high output and capacity, is particularly popular. Mobile phones, smartphones, notebook computers and other portable information terminals, portable music devices Players, digital cameras, medical equipment, or hybrid vehicles (HEVs), electric vehicles ( Next-generation clean energy such as electric vehicles (EV) or plug-in hybrid vehicles (PHEV) Demand for rechargeable energy has expanded rapidly along with the development of the semiconductor industry, including automobiles. It has become an indispensable source of information in today's information society.
[0005] Currently, the characteristics required for lithium-ion secondary batteries are higher capacity and cycle time. These include improved module characteristics, safety in various operating environments, and improved long-term reliability.
[0006] Therefore, in order to improve the cycle characteristics and capacity of lithium-ion secondary batteries, Improvements to active materials have been investigated (Patent Document 1, Patent Document 2, and Patent Document 3). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 8-236114 [Patent Document 2] JP 2002-124262 A [Patent Document 3] JP 2002-358953 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, lithium ion secondary batteries and the positive electrode active materials used therein have a cycle There are still many aspects to be improved, such as characteristics, capacity, charge / discharge characteristics, reliability, safety, and cost. There is still room for improvement.
[0009] One embodiment of the present invention is to improve the efficiency of charge / discharge cycles by using the same in a lithium ion secondary battery. Another object of the present invention is to provide a positive electrode active material in which the decrease in the amount of the positive electrode active material is suppressed. Another object of the present invention is to provide a high-capacity secondary battery. Another object of the present invention is to provide a secondary battery having excellent charge and discharge characteristics. An object of the present invention is to provide a secondary battery with high safety and reliability.
[0010] Another embodiment of the present invention provides a novel substance, an active material, a power storage device, or a manufacturing method thereof. One of our goals is to provide
[0011] The description of these problems does not preclude the existence of other problems. It is not necessary for the embodiment to solve all of these problems. It is possible to extract problems other than those mentioned above from the description of the claim. [Means for solving the problem]
[0012] In order to achieve the above object, one aspect of the present invention is to provide a cathode active material having a surface layer portion to which aluminum is added. The present invention is characterized in that a coating layer containing titanium and a coating layer containing magnesium are provided.
[0013] One embodiment of the present invention is a positive electrode active material, the positive electrode active material including a first region, a second region, and and a third region, the first region being present inside the positive electrode active material, and the second region being present inside the first a third region covering at least a portion of the second region; and a third region covering at least a portion of the second region; The first region has lithium, a transition metal, and oxygen, and the second region has lithium and aluminium. The first region has aluminum, a transition metal, and oxygen, and the third region has magnesium and oxygen. It is a positive electrode active material having the above structure.
[0014] In the above, the third region may contain fluorine.
[0015] In the above, the third region may contain a transition metal.
[0016] In the above, the first region and the second region have a layered rock salt type crystal structure, and the third region has a layered rock salt type crystal structure. The region may have a rock-salt type crystal structure.
[0017] In the above, the transition metal may be cobalt.
[0018] Another embodiment of the present invention is a positive electrode active material, the positive electrode active material being a mixture of lithium and aluminum. A surface layer of a positive electrode active material is provided with a transition metal, magnesium, oxygen, and fluorine. Lithium, aluminum, transition metals, and magnesium are present and measured by X-ray photoelectron spectroscopy. The total amount of oxygen and fluorine is taken as 100 atomic %, and it is present in the surface layer of the positive electrode active material. The aluminum concentration, as measured by photoelectron spectroscopy, is 0.1 atomic % or more and 10 atomic % or less, Magnesium concentration is 5 atomic % or more and 20 atomic % or less, and fluorine concentration is 3.5 atomic % or more The positive electrode active material has a content of 14 atomic % or less.
[0019] Another embodiment of the present invention is a battery including a positive electrode having the above-described positive electrode active material, a negative electrode, an electrolyte, and an outer casing. and a secondary battery having the above structure.
[0020] Further, one aspect of the present invention is a method for producing a solubility-type aluminum alkoxide by dissolving an aluminum alkoxide in an alcohol. Aluminum alkoxide is dissolved in alcohol. A particle having lithium, a transition metal, magnesium, oxygen, and fluorine in a sol. mixing an alcohol solution of aluminum alkoxide, lithium, and a transition metal A mixture of particles having metal, magnesium, oxygen, and fluorine is added to water. A step of stirring in an atmosphere containing steam, a step of recovering a precipitate from the mixed liquid, and a step of recovering the precipitate from the mixed liquid. The precipitate was heated in an oxygen-containing atmosphere at 500°C to 1200°C for 50 hours or more. and heating the cathode active material under reduced pressure. Effect of the Invention
[0021] According to one embodiment of the present invention, by using the compound in a lithium ion secondary battery, It is possible to provide a positive electrode active material in which the capacity reduction caused by the charging is suppressed. It is also possible to provide a secondary battery having excellent charge / discharge characteristics. In addition, a secondary battery having high safety and reliability can be provided. A substance, a power storage device, or a method for manufacturing the same can be provided. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 illustrates an example of a positive electrode active material. [Diagram 2] 1A to 1C illustrate an example of a method for manufacturing a positive electrode active material. [Diagram 3] FIG. 13 is a cross-sectional view of an active material layer in the case where a graphene compound is used as a conductive assistant. [Figure 4] FIG. 2 is a diagram illustrating a coin-type secondary battery. [Diagram 5] FIG. 2 is a diagram illustrating a cylindrical secondary battery. [Figure 6] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 7] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 8] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 9] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 10] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 11] FIG. 1 is a diagram illustrating a laminated secondary battery. [Figure 12] FIG. 1 is a diagram illustrating a laminated secondary battery. [Figure 13]FIG. 2 is a diagram showing the appearance of a secondary battery. [Figure 14] FIG. 2 is a diagram showing the appearance of a secondary battery. [Figure 15] 1A to 1C are diagrams illustrating a method for manufacturing a secondary battery. [Figure 16] 1A and 1B are diagrams illustrating a bendable secondary battery. [Figure 17] 1A and 1B are diagrams illustrating a bendable secondary battery. [Figure 18] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 19] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 20] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 21] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 22] 3 is a graph showing cycle characteristics of a secondary battery using the positive electrode active material of Example 1. [Diagram 23] 1 is a STEM image of the positive electrode active material of Example 2. [Figure 24] 1 is a STEM-FFT image of the positive electrode active material of Example 2. [Diagram 25] 4 is a STEM image and EDX elemental mapping of the positive electrode active material of Example 2. [Figure 26] 4 is a STEM image and EDX line analysis of the positive electrode active material of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. The present invention is not limited to the following description, and various modifications in form and details are possible by those skilled in the art. The present invention is not limited to the description of the following embodiments. It is not something that can be done.
[0024] In this specification, crystal planes and directions are indicated by Miller indices. In the above, the numbers are marked with superscript bars in crystallography, but the crystal planes and directions in this specification are Due to restrictions on the notation of the application, instead of putting a bar above the numbers, a minus sign (-) is put before the numbers. In addition, individual directions that indicate directions within a crystal are expressed in [ ], and all equivalent directions are expressed in [ ]. The aggregate orientation is indicated by < >, the individual crystal faces are indicated by ( ), and the aggregates with equivalent symmetry are indicated by ( Each joint is represented by {}.
[0025] In this specification, segregation refers to a phenomenon in which a solid consisting of multiple elements (e.g., A, B, C) This refers to the phenomenon in which a certain element (such as B) is distributed unevenly.
[0026] In the present specification and the like, the layered rock-salt type crystal structure of a composite oxide containing lithium and a transition metal is The structure has a rock-salt type ion arrangement in which cations and anions are arranged alternately, and the transition metal and lithium The lithium atoms are regularly arranged to form a two-dimensional plane, allowing two-dimensional diffusion of lithium. The term refers to a crystal structure. It is acceptable for there to be defects such as deficiencies of cations or anions. Strictly speaking, the rock salt crystal structure is a distorted structure of the rock salt crystal lattice. be.
[0027] In the present specification and the like, a rock salt type crystal structure is a structure in which cations and anions are arranged alternately. The structure may contain a cation or anion defect.
[0028] Layered rock salt crystals and anions in rock salt crystals form a cubic close-packed structure (face-centered cubic lattice structure). When layered rock salt crystals come into contact with each other, the cubic close-packed structure of anions is formed. However, the space group of the layered rock salt crystal is R-3m. The space groups of rock salt crystals are Fm-3m (the general space group of rock salt crystals) and Fd-3m ( Since the space group is different from that of the rock salt type crystals, which have the simplest symmetry, the above conditions are satisfied. The Miller indices of the crystal planes are different between layered rock-salt crystals and rock-salt crystals. In crystals and rock salt crystals, the cubic close-packed structure formed by anions is oriented in the same direction. When this occurs, it is said that the crystal orientation is roughly the same.
[0029] The alignment of the crystal orientations in the two regions is confirmed by TEM (transmission electron microscope) and STEM (scanning electron microscope) images. High-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image, ) images, ABF-STEM (annular bright-field scanning transmission electron microscope) images, etc. X-ray diffraction, electron diffraction, neutron diffraction, etc. can also be used for judgment. TEM image In rocks such as these, the arrangement of cations and anions can be observed as repeated bright and dark lines. When the orientation of the cubic close-packed structure of salt-type crystals and rock salt-type crystals is aligned, bright and dark lines appear between the crystals. It can be observed that the angle between the repeats is 5 degrees or less, and more preferably 2.5 degrees or less. In addition, light elements such as oxygen and fluorine may not be clearly observed in TEM images. In some cases, the alignment can be determined by the arrangement of the metal elements.
[0030] (Embodiment 1) [Positive electrode active material structure] First, a positive electrode active material 100 according to one embodiment of the present invention will be described with reference to FIG. As shown in FIG. 1(B) and FIG. 1(C), the positive electrode active material 100 is composed of a first region 101 and a second region 102. The first region 101 is located inside the positive electrode active material 100. The second region 102 covers at least a portion of the first region 101. The region 103 covers at least a portion of the second region 102 .
[0031] As shown in FIG. 1B, even if a third region 103 exists inside the positive electrode active material 100, For example, when the first region 101 is polycrystalline, the third region 103 exists near the grain boundary. In addition, the third region 1 may be present in the vicinity of the portion of the positive electrode active material 100 having the crystal defect. In FIG. 1, a part of the grain boundary is shown by a dotted line. A crystal defect is a defect that can be observed in a TEM image, i.e. a structure in which other elements have entered the crystal. , cavities, etc.
[0032] Although not shown, the positive electrode active material 100 may have a second region 102 inside. For example, when the first region 101 is polycrystalline, the second region 102 exists near the grain boundary. In addition, the second region 102 may be present in the vicinity of the portion of the positive electrode active material 100 having the crystal defect. It may be possible.
[0033] In addition, the second region 102 does not have to cover the entire first region 101. The third region 103 does not necessarily cover the entire second region 102. Adjacent to region 101, there may be a third region 103.
[0034] In other words, the first region 101 exists inside the positive electrode active material 100, and the second region 10 The second and third regions 103 are present in the surface layer portion of the positive electrode active material 100. The region 102 and the third region 103 function as a coating layer for the positive electrode active material. The region 103 and the second region 102 may be present inside the particle of the positive electrode active material 100. good.
[0035] If the particle size of the positive electrode active material 100 is too large, it becomes difficult for lithium to diffuse. On the other hand, if the size is too small, the surface of the active material layer becomes too rough. Problems such as difficulty in coating the surface and excessive reaction with the electrolyte may occur. 50 (also called the median diameter) is preferably 0.1 μm or more and 100 μm or less, and more preferably 1 μm or less. It is more preferable that the thickness is at most 40 μm.
[0036] In order to increase the density of the positive electrode active material layer, large particles (approximately 20 μm or more, approximately 40 μm or more) are required. The particles are mixed with small particles (approximately 1 μm) and the gaps between the larger particles are filled with the smaller particles. Therefore, the particle size distribution may have two or more peaks.
[0037] <First Region 101> The first region 101 includes lithium, a transition metal, and oxygen. It may be said that the material has a composite oxide containing lithium and a transition metal.
[0038] The transition metal contained in the first region 101 is a layered rock salt type composite oxide together with lithium. It is preferable to use a metal capable of forming the above-mentioned metals. For example, manganese, cobalt, nickel, etc. In other words, the transition metal in the first region 101 and Cobalt alone may be used, or both cobalt and manganese may be used. Alternatively, the first region 101 may be formed of three types of metals, i.e., zinc, manganese, and nickel. In addition, metals other than transition metals, such as aluminum, may be contained.
[0039] That is, the first region 101 is made of lithium cobalt oxide, lithium nickel oxide, and a part of cobalt. Lithium cobalt oxide with manganese substitution, lithium nickel-manganese-cobalt oxide Lithium-cobalt-aluminum oxide and other composite acids containing lithium and transition metals The compound may have a structure similar to that of the compound of the present invention.
[0040] The first region 101 is a region of the positive electrode active material 100 that particularly contributes to the charge / discharge reaction. In order to increase the capacity of a secondary battery when the positive electrode active material 100 is used, the first region 101 is , preferably has a larger volume than the second region 102 and the third region 103.
[0041] The first region 101 may be a single crystal or a polycrystal. The powder 1 may be polycrystalline with an average crystallite size of 280 nm or more and 630 nm or less. In the case of crystals, the grain boundaries can be observed using a TEM. The average grain size is It can be calculated from the half-width of XRD.
[0042] Since polycrystals have a clear crystal structure, there are sufficient paths for two-dimensional diffusion of lithium ions. In addition, it is easier to produce than a single crystal, and therefore is preferable for the first region 101. stomach.
[0043] Since lithium easily diffuses two-dimensionally in the layered rock salt crystal structure, the first region 101 is preferably made of the layered rock salt crystal structure. Moreover, when the first region 101 has a layered rock salt type crystal structure, the following is unexpectedly However, the entire first region 101 is made of layered rock salt. For example, the first region 101 may have a crystal defect in part. Alternatively, a part of the first region 101 may be amorphous, or the first region 101 may be a non-crystalline region. It may have a crystalline structure.
[0044] <Second Region 102> The second region 102 includes lithium, aluminum, a transition metal, and oxygen. In the composite oxide containing aluminum and a transition metal, some of the transition metal sites are replaced by aluminum. The transition metal contained in the second region 102 is different from the transition metal contained in the first region 101. In this specification, the term "site" refers to a transition metal that is bonded to the This refers to the position that a certain element should occupy in a crystal.
[0045] The second region 102 may also contain fluorine.
[0046] The second region 102 contains aluminum, which improves the cycle characteristics of the positive electrode active material 100. The aluminum in the second region 102 has a concentration gradient. Aluminum may be a part of a composite oxide containing lithium and a transition metal. It is preferable that it exists at the transition metal site, but it may exist in other states. For example, it may exist as aluminum oxide (Al2O3).
[0047] In general, the positive electrode active material loses transition metals such as cobalt and manganese as it is repeatedly charged and discharged. Side reactions occur, such as dissolution into the electrolyte, oxygen release, and the crystal structure becoming unstable. However, the positive electrode active material 100 according to one embodiment of the present invention has an aluminum surface layer. Since the second region 102 has lithium, the transition occurs between the lithium in the first region 101 and the lithium in the second region 102. It is possible to make the crystal structure of the complex oxide containing the transition metal more stable. The cycle characteristics of a secondary battery containing the material 100 can be improved.
[0048] The second region 102 preferably has a layered rock salt type crystal structure. Since the layered rock salt type crystal structure is formed, the first region 101 and the third region 103 are bonded to each other. The crystal orientation of the first region 101, the second region 102, and the third region 103 are easily aligned. When the crystal orientations of the first and second regions 102 and 103 are roughly aligned, the second and third regions 102 and 103 are more stable. It can function as a fixed covering layer.
[0049] If the second region 102 is too thin, its function as a covering layer is reduced, but if it is too thick, the second region 102 cannot be easily covered. Therefore, the second region 102 is formed by separating the positive electrode active material 100 from the surface of the positive electrode active material 100. It is preferable that the thickness of the thin film is within 30 nm, and more preferably within 15 nm, in the depth direction from the surface of the thin film.
[0050] <Third Area 103> The third region 103 includes magnesium and oxygen. The third region 103 is a magnesium oxide. It can be said to contain nesium.
[0051] The third region 103 contains the same transition metal as the first region 101 and the second region 102. Furthermore, the third region 103 may contain fluorine. When 103 has fluorine, some of the oxygen in magnesium oxide is replaced by fluorine. Good too.
[0052] Since the magnesium oxide contained in the third region 103 is an electrochemically stable material, it is possible to charge and discharge the The positive electrode active material 100 is suitable as a coating layer because it is less likely to deteriorate even when the positive electrode is repeatedly charged. By having the third region 103 in addition to the second region 102 in the surface layer portion, It is possible to make the crystal structure of the composite oxide containing lithium and transition metals of 1 more stable. Therefore, it is possible to improve the cycle characteristics of a secondary battery having the positive electrode active material 100. Also, 4.3V (vs. Li / Li + ), especially voltages exceeding 4.5V (v s. Li / Li + When charging and discharging is performed at a high voltage of 100 V or more, the structure of one embodiment of the present invention is particularly It has a significant effect.
[0053] When the third region 103 has a rock salt type crystal structure, the crystal orientation is the same as that of the second region 102. This is preferable because it is easy to adhere to the surface of the third region 10 and it is easy to function as a stable coating layer. The third region 103 does not necessarily have to have a rock-salt crystal structure. The third region 103 may have any other crystal structure.
[0054] If the third region 103 is too thin, its function as a covering layer is reduced, but if it is too thick, the third region 103 cannot be easily covered. Therefore, the third region 103 is It is preferable that the thickness is 0.5 nm or more and 50 nm or less, and it is preferable that the thickness is 0.5 nm or more and 5 nm or less. It is more preferable that the
[0055] It is important that the third region 103 contains an electrochemically stable material. The element to be used does not necessarily have to be magnesium. For example, instead of magnesium, In addition to magnesium, it may also contain typical elements such as calcium and beryllium. Furthermore, instead of or together with fluorine, chlorine may be contained.
[0056] <Boundaries between each area> The first region 101, the second region 102, and the third region 103 are regions having different compositions. However, the elements in each region may have a concentration gradient. For example, The aluminum in the second region 102 may have a concentration gradient. As will be described later, 103 is preferably a region where magnesium is segregated. There may be a gradient of the concentration of nesium. Therefore, the boundaries between the regions are not clear. There are cases.
[0057] The first region 101, the second region 102, and the third region 103 are used for a TEM image, a STEM image, and , FFT (Fast Fourier Transform) analysis, EDX (Energy Dispersive X-ray Analysis), ToF-S Depth analysis by IMS (time-of-flight secondary ion mass spectrometry), XPS (X-ray photoelectron Spectroscopy), Auger electron spectroscopy, TDS (thermal desorption spectroscopy), etc. It can be confirmed that the EDX measurement is performed while scanning the area. Two-dimensional evaluation is sometimes called EDX area analysis. The data in the region was extracted and the distribution of atomic concentration within the positive electrode active material particles was evaluated. This is sometimes called analysis.
[0058] For example, in TEM and STEM images, differences in the constituent elements appear as differences in the brightness of the images. Therefore, the constituent elements of the first region 101, the second region 102, and the third region 103 In addition, surface analysis by EDX (e.g. element mapping) also reveals that the first It is observed that the first region 101, the second region 102 and the third region 103 have different elements. I can understand.
[0059] In addition, line analysis by EDX and depth direction analysis by ToF-SIMS revealed that the first region 101, the peaks of the concentrations of the elements in the second region 102 and the third region 103 are detected. It is possible.
[0060] However, it is not necessarily the case that the first region 101, the second region 102, and the third region are determined by various analyses. It is not necessary that a clear boundary of the region 103 is observable.
[0061] In this specification, the range of the third region 103 present in the surface layer portion of the positive electrode active material 100 is This refers to the time from the surface of the positive electrode active material 100 until the magnesium concentration reaches 1 / 5 of its peak. The analytical methods used were the above-mentioned EDX line analysis and ToF-SIMS. Depth analysis etc. can be applied.
[0062] The peak of magnesium concentration is at a depth of 3 mm from the surface to the center of the positive electrode active material 100. Preferably, the ions are present in the range of 1 nm to a depth of 20 nm, more preferably in the range of 1 nm to a depth of 20 nm. It is more preferable that the thickness is within 0.5 nm.
[0063] The depth at which the magnesium concentration becomes 1 / 5 of the peak varies depending on the manufacturing method, but will be described later. In the case of the manufacturing method, the thickness is generally about 2 nm to 5 nm from the surface of the positive electrode active material.
[0064] The third region 103 present inside the first region 101 was also detected by the depth profile analysis. This refers to the region where the concentration of the typical element detected is 1 / 5 or more of the peak.
[0065] The distribution of fluorine in the positive electrode active material 100 preferably overlaps with the distribution of magnesium. Therefore, fluorine also has a concentration gradient, and the peak of the fluorine concentration occurs at the positive electrode active material 100. It is preferable that the surface is located within a depth of 3 nm toward the center, and the depth is preferably within a depth of 1 nm. It is more preferable that the pores are present at a depth of up to 0.5 nm, and it is even more preferable that the pores are present at a depth of up to 0.5 nm.
[0066] In the present specification and the like, the second region 102 present in the surface layer portion of the positive electrode active material 100 is This refers to the area where the aluminum concentration detected by the depth analysis is more than half of the peak. The second region 101 exists inside the first region 101, such as near the grain boundary or near the crystal defect. For 02, the aluminum concentration detected by depth profile analysis was more than half the peak. The analytical methods used were the above-mentioned EDX line analysis and ToF. -SIMS-based depth analysis can be applied.
[0067] Therefore, the third region 103 and the second region 102 may overlap each other. The region 103 is located closer to the surface of the particle of the positive electrode active material than the second region 102. In addition, the peak of magnesium concentration is more positive than the peak of aluminum concentration. It is preferred that the metal oxide is present in a region close to the surface of the particles of the electrode active material.
[0068] The aluminum concentration peaks at a depth of 0.5n from the surface to the center of the positive electrode active material 100. Preferably, the nanoparticles are present at a depth of 1 nm to 5 nm. is more preferable.
[0069] The concentrations of aluminum, magnesium, and fluorine were measured by ToF-SIMS, EDX, and the like. In addition to surface and line analysis, XPS, Auger electron spectroscopy, TDS, etc. are also used for analysis. This can be done.
[0070] In addition, the measurement range of XPS is about 5 nm from the surface of the positive electrode active material 100. It is possible to quantitatively analyze the concentration of elements present in the region from 10 to 5 nm. When the thickness of the third region 103 is less than 5 nm from the surface, a part of the second region 102 When the thickness of the third region 103 is 5 nm or more from the surface, the third region 10 3. The element concentrations can be quantitatively analyzed.
[0071] Lithium, aluminum, and the first region measured by XPS from the surface of the positive electrode active material 100 The total amount of transition metals, magnesium, oxygen, and fluorine contained in 101 is taken as 100 atomic %. When the aluminum concentration is 0.1 atomic % or more and 10 atomic % or less, It is more preferable that the magnesium concentration is 0.1 atomic % or more and 2 atomic % or less. The fluorine concentration is preferably 3.5 atomic % or more and 14 atomic % or less. It is preferable that the content is 1 atomic % or less.
[0072] As described above, the first region 101, the second region 102, and the third region 103 have Since elements may have a concentration gradient, the first region 101 may be divided into the second region 102 and The third region 103 may have the same element as the first region 103. The first region 101 and the second region 102 may have the same elements. 101, the second region 102 and the third region 103 are carbon, sodium, calcium, It may contain other elements such as chlorine and zirconium.
[0073] [Covering the second area] The second region 102 is made of particles of a composite oxide containing lithium and a transition metal, and aluminum is added to the particles. The insulating layer can be formed by coating a material having the above-mentioned properties.
[0074] Methods for coating aluminum-containing materials include liquid phase methods such as the sol-gel method, Solid-phase method, sputtering method, deposition method, CVD (chemical vapor deposition) method, PLD (pulsed laser In this embodiment, a uniform coating is expected. The sol-gel method, which allows processing at atmospheric pressure and can be performed after a long time, will be applied.
[0075] When the sol-gel method is applied, aluminum alkoxide is first dissolved in alcohol, and the solution is Particles of a composite oxide containing lithium and a transition metal are mixed into the liquid and stirred in an atmosphere containing water vapor. By placing it in an atmosphere containing H2O, composite oxide particles containing lithium and transition metals are formed. On the surface of the particles, hydrolysis and polycondensation reactions between water and aluminum alkoxide occur, A gel-like layer containing aluminum is formed on the surface, after which the particles are collected and dried. The details of the manufacturing method will be described later.
[0076] In this embodiment, particles of a composite oxide containing lithium and a transition metal are coated on a positive electrode current collector. Before the process, an example of coating an aluminum-containing material was described. The method is not limited to this. After forming a positive electrode active material layer containing aluminum alkoxide, the positive electrode current collector and the positive electrode active material layer are It may also be soaked in a solution containing cid.
[0077] [Segregation in the third region] The third region 103 is a region including a sputtering method, a solid phase method, a liquid phase method such as a sol-gel method, etc. However, the present inventors have found that the magnesium source and the fluorine source are first After mixing with the material in region 101 of FIG. 1, the magnesium is mixed with the material in region 102 of FIG. 1 by heating. It was revealed that the third region 103 was formed by segregating to the outermost surface. The positive electrode active material 100 having the third region 103 formed therein has excellent cycle characteristics. It was revealed that
[0078] By heating as described above, magnesium is segregated on the outermost surface of the positive electrode active material particles, and the third In forming region 103, heating is performed to dissolve lithium, transition metals, magnesium, and fluorine. It is preferable to coat the composite oxide particles having the above structure with a material containing aluminum before the coating. Surprisingly, even after coating with the aluminum-containing material, magnesium remained in the positive electrode active material particles. This is because the oxide segregates onto the outermost surface of the substrate. The details of the preparation method will be described later.
[0079] When magnesium is segregated, the complex containing lithium and a transition metal in the first region 101 is When the oxide is polycrystalline or has crystal defects, the lithium and Magnesium can also segregate near grain boundaries and crystal defects in composite oxides containing transition metals. The magnesium segregated near the boundary or the crystal defect combines with the lithium contained in the first region 101. This can contribute to further stabilization of the crystal structure of the composite oxide containing a transition metal.
[0080] The ratio of magnesium to fluorine in the raw materials is Mg:F=1:x (1.5≦x≦4) (atomic ratio). In the range of Mg:F=1:, magnesium segregation occurs effectively. It is more preferable that the atomic ratio is about 2.
[0081] The third region 103 formed by segregation is formed by epitaxial growth. Therefore, the crystal orientations of the second region 102 and the third region 103 may partly roughly coincide with each other. That is, the second region 102 and the third region 103 may be topotaxis. When the crystal orientations of the region 102 and the third region 103 are roughly the same, they are more favorable. It can function as a covering layer.
[0082] In the present specification and the like, the term "having three-dimensional structural similarity" refers to "having crystallographic similarity" or "having crystallographic similarity." The same orientation is called topotaxis. In other words, the crystals in two regions (for example, the base region and the region that is formed by growth) The orientations are roughly the same.
[0083] <Fourth Area 104> In the above, the positive electrode active material 100 is divided into a first region 101, a second region 102, and a third region. Although an example having the 103 has been described, one embodiment of the present invention is not limited to this. For example, FIG. As shown in (C), the positive electrode active material 100 may have a fourth region 104. The region 104 is provided, for example, so as to be in contact with at least a part of the third region 103. The fourth region 104 is a film containing carbon such as a graphene compound. Alternatively, the coating may be a coating having a decomposition product of lithium or the electrolyte. When the region 104 is a coating having carbon, the positive electrode active material 100 and the positive electrode active material 1 In addition, the fourth region 104 can increase the electrical conductivity between the lithium ion battery 100 and the current collector. In the case of a coating containing a decomposition product of the electrolyte, excessive reaction with the electrolyte is suppressed, and the secondary battery When used in the above, the cycle characteristics can be improved.
[0084] [Production method] Positive electrode active material having a first region 101, a second region 102 and a third region 103 An example of a method for producing the substrate 100 will be described with reference to FIG. One region has cobalt as the transition metal and the second region uses aluminum alkoxide. It is formed through the sol-gel method. It is then heated to cause magnesium to segregate on the surface. These are combined to form the third region 103 .
[0085] First, starting materials are prepared (S11). The starting materials include lithium, cobalt, and fluorine. The present invention uses particles of a composite oxide containing magnesium.
[0086] When synthesizing composite oxide particles containing lithium, cobalt, fluorine, and magnesium, First, the lithium source, the cobalt source, the magnesium source, and the fluorine source are weighed out. The lithium source may be, for example, lithium carbonate, lithium fluoride, lithium hydroxide, etc. The cobalt source can be, for example, cobalt oxide, cobalt hydroxide, cobalt oxyhydroxide, etc. Baltic, cobalt carbonate, cobalt oxalate, cobalt sulfate, etc. can be used. As the magnesium source, for example, magnesium oxide, magnesium fluoride, etc. can be used. As the fluorine source, for example, lithium fluoride, magnesium fluoride, etc. can be used. In other words, lithium fluoride can be used as both a lithium source and a fluorine source. Magnesium fluoride can be used both as a magnesium source and as a fluorine source. There can be.
[0087] The atomic ratio of magnesium to fluorine in the raw materials is preferably Mg:F=1:x (1.5≦x≦4). It is more preferable that the atomic ratio is about Mg:F=1:2. If there is any, magnesium segregation is likely to occur when heating is performed in a later process.
[0088] Next, the weighed starting materials are mixed. For example, a ball mill, a bead mill, etc. are used for mixing. It is possible.
[0089] Next, the mixed starting materials are sintered. The sintering is preferably carried out at a temperature of 800° C. or higher and 1050° C. or lower. It is preferable to perform the firing at a temperature of 900° C. or higher and 1000° C. or lower. The firing time is 2 hours or less. The firing time should be no longer than 20 hours. The firing should be carried out in a dry atmosphere such as dry air. As a dry atmosphere, for example, a dew point of -50°C or less is preferable, and a dew point of -10 An atmosphere of 0° C. or less is more preferable. In this embodiment, heating is performed at 1000° C. for 10 hours. The temperature rise is 200℃ / h, and dry air with a dew point of -109℃ is supplied at 10L / min. The heated material is then cooled to room temperature.
[0090] In the above process, particles of a composite oxide containing lithium, cobalt, fluorine, and magnesium are mixed. It can be achieved.
[0091] The starting material is a composite oxide of lithium and cobalt that has already been synthesized. For example, lithium cobalt oxide particles (trade name) manufactured by Nippon Chemical Industry Co., Ltd. may be used. :C-20F) can be used as the starting material. It has a particle size of about 20 μm, Fluorine, magnesium, calcium, sodium, and silicon are detected in the area that can be analyzed by XPS from the surface. The starting material is lithium cobalt oxide particles containing silicon, sulfur, and phosphorus. The lithium cobalt oxide particles (product name: C-20F) manufactured by Nippon Chemical Industry Co., Ltd. were used as the It will be used.
[0092] Next, aluminum alkoxide is dissolved in alcohol, and the starting material particles are mixed with the solution. (S12).
[0093] Aluminum alkoxides include trimethoxyaluminum and triethoxyaluminum. Aluminum, tri-n-propoxyaluminum, tri-i-propoxyaluminum, tri- n-Butoxyaluminum, tri-i-butoxyaluminum, tri-sec-butoxy Aluminum, tri-t-butoxyaluminum, etc. can be used. Aluminum Solvents that dissolve alkoxides include methanol, ethanol, propanol, 2- Propanol, butanol, 2-butanol, etc. can be used.
[0094] The alkoxide group of the aluminum alkoxide and the alcohol used as the solvent are different. Although combinations of different types may be used, it is particularly preferred that the types are the same.
[0095] Next, the mixture is stirred in an atmosphere containing water vapor (S13). H2O and aluminum isopropoxide in the atmosphere undergo hydrolysis and polycondensation reactions. The surface of the lithium cobalt oxide particles containing magnesium and fluorine is coated with gel-like aluminum. A layer containing nium is formed.
[0096] The stirring can be performed, for example, by using a magnetic stirrer. The stirring time is determined by the water content of the atmosphere. and aluminum isopropoxide for a period of time sufficient to cause hydrolysis and polycondensation reactions. For example, 4 hours, 25℃, 90% RH (Relative Humidity) The test can be performed under conditions of (ty, relative humidity).
[0097] As described above, by reacting aluminum alkoxide with water at room temperature, for example, a solvent When heating to a temperature above the boiling point of alcohol (for example, 100°C or higher), It is possible to form a coating layer containing aluminum that is more uniform and of better quality.
[0098] The precipitate is collected from the mixed liquid after the above treatment (S14). The collection method is filtration. In this embodiment, the particles are collected by filtration. A paper filter was used for filtration, and the residue was filtered with a solvent containing aluminum alkoxide. The mixture should be washed with the same alcohol as the medium.
[0099] Next, the collected residue is dried (S15). In this embodiment, the residue is dried in a vacuum at 70° C. for 1 hour. It will be dried.
[0100] Next, the dried powder is heated (S16). By this heating, the magnesium contained in the starting material is dissolved. Sium and fluorine segregate to the surface to form third regions 103 .
[0101] Heating is preferably performed for a holding time of 50 hours or less at the specified temperature, and is preferably performed for 1 hour to 10 hours. It is more preferable to maintain the temperature at the specified temperature or below. The temperature is preferably 500° C. or higher and 1200° C. or lower, and more preferably 700° C. or higher and 1000° C. or lower. It is preferable to heat the material at a temperature of about 800° C., and more preferable to heat the material at a temperature of about 800° C. In addition, it is preferable to heat the material in an atmosphere containing oxygen. In this embodiment, the specified temperature is set to 800° C. and is maintained for 2 hours. The temperature is 200℃ / h, and the flow rate of dry air is 10L / min. The cooling time is the same as or shorter than the heating time. This will take the above amount of time.
[0102] Next, it is preferable to cool the heated powder and perform a crushing process (S17). This can be done, for example, by sieving.
[0103] Through the above steps, the positive electrode active material 100 of one embodiment of the present invention can be manufactured.
[0104] (Embodiment 2) In this embodiment, a secondary battery having the positive electrode active material 100 described in the previous embodiment is used. In this embodiment, the positive electrode, the negative electrode, and the electrolyte are Here, a secondary battery enclosed in an exterior body will be taken as an example.
[0105] [Positive electrode] The positive electrode has a positive electrode active material layer and a positive electrode current collector.
[0106] <Cathode active material layer> The positive electrode active material layer includes a positive electrode active material. The positive electrode active material layer also includes a conductive assistant and a binder.
[0043]
[0107] As the positive electrode active material, the positive electrode active material 100 described in the previous embodiment can be used. By using the positive electrode active material 100 described in the previous embodiment, it is possible to obtain a high capacity and good cycle characteristics. This makes it possible to produce an excellent secondary battery.
[0108] As the conductive assistant, a carbon material, a metal material, a conductive ceramic material, or the like can be used. In addition, a fibrous material may be used as the conductive assistant. The content of the electrical auxiliary agent is preferably 1 wt% or more and 10 wt% or less, and more preferably 1 wt% or more and 5 wt% or less. is more preferred.
[0109] The conductive additive can form an electrically conductive network in the electrode. This makes it possible to maintain a path of electrical conduction between the positive electrode active materials. By adding the agent, an active material layer having high electrical conductivity can be realized.
[0110] Examples of the conductive assistant include natural graphite, artificial graphite such as mesocarbon microbeads, and carbon fibers. Examples of carbon fibers that can be used include mesophase pitch carbon fibers. In addition, carbon fibers such as isotropic pitch-based carbon fibers can be used. Carbon nanofibers and carbon nanotubes can be used. The tube can be produced by, for example, a vapor phase growth method. For example, carbon black (acetylene black (AB) etc.), graphite particles Carbon materials such as copper, nickel, and graphene can be used. Nickel, aluminum, silver, gold and other metal powders, metal fibers, conductive ceramic materials, etc. It can be used.
[0111] In addition, a graphene compound may be used as the conductive assistant.
[0112] Graphene compounds have excellent electrical properties, such as high electrical conductivity, as well as high flexibility and In addition, graphene may have excellent physical properties such as high mechanical strength. The compound has a planar shape. Graphene compounds enable surface contact with low contact resistance. In addition, even if the material is thin, it can have very high conductivity, and a small amount of the material can be used to efficiently conduct electricity within the active material layer. Therefore, the graphene compound can be used as a conductive additive. This is preferable because it is possible to increase the contact area between the active material and the conductive assistant. In this case, the graphene compound is preferably a graphene compound having a low electrical resistance. For example, graphene or multi-graphene or reduced graphene O It is particularly preferred to use RGO oxide. This refers to a compound obtained by reducing graphene oxide (GO).
[0113] When using an active material with a small particle size, for example, an active material with a particle size of 1 μm or less, the specific surface area of the active material is Therefore, a large amount of conductive additive is required. This tends to result in a relatively reduced amount of active material carried. If the capacity of the secondary battery decreases, the capacity of the secondary battery decreases. When graphene compounds are used, they efficiently form conductive paths even in small amounts. This is particularly preferable because it is possible to avoid reducing the amount of the active material carried.
[0114] In the following, as an example, a graphene compound is used as a conductive assistant in the active material layer 200. An example of the cross-sectional structure will be described.
[0115] 3A shows a vertical cross-sectional view of the active material layer 200. The active material layer 200 is made of granular positive electrode active material. 100, a graphene compound 201 as a conductive assistant, and a binder (not shown). Here, the graphene compound 201 may be, for example, graphene or multi-graphene. Here, the graphene compound 201 preferably has a sheet shape. In addition, the graphene compound 201 may include a plurality of multi-graphenes or (and) a plurality of The graphene may be partially overlapped to form a sheet.
[0116] In the vertical cross section of the active material layer 200, as shown in FIG. In FIG. 3(A), the sheet-like graphene compound 201 is dispersed almost uniformly. The graphene compound 201 is shown in bold in schematic form, but in reality it is a single or multiple layer of carbon molecules. The graphene compounds 201 are thin films having a thickness of 100 nm. The positive electrode active material 100 is wrapped or covered with the positive electrode active material 100 or on the surface of the positive electrode active material 100. Since they are formed to stick to each other, they are in surface contact with each other.
[0117] Here, a plurality of graphene compounds are bonded to each other to form a mesh-like graphene compound. The graphene compound is then bonded to the graphene sheet (hereinafter referred to as a graphene compound net or a graphene net). When the active material is covered with a graphene net, the graphene net can bond the active material to each other. It can also function as a binder to bind the material together. This allows the amount of binder to be reduced. The ratio of active material to the electrode volume or weight can be adjusted to suit the application. In other words, the capacity of the power storage device can be increased.
[0118] Here, graphene oxide is used as the graphene compound 201, and is mixed with an active material to form an active material. After the layer that will become the layer 200 is formed, it is preferable to reduce it. By using graphene oxide, which has extremely high dispersibility in polar solvents, The mixture 201 can be dispersed approximately uniformly inside the active material layer 200. The solvent is removed by evaporation from the dispersion medium containing the dispersed graphene oxide, and the graphene oxide is reduced. Therefore, the graphene compounds 201 remaining in the active material layer 200 are partially overlapped with each other. By dispersing the particles so that they are in surface contact with each other, a three-dimensional conductive path can be formed. The reduction of graphene oxide may be performed, for example, by heat treatment or by using a reducing agent. This is also possible.
[0119] Therefore, unlike granular conductive additives such as acetylene black, which come into point contact with the active material, graphite Since the compound 201 enables surface contact with low contact resistance, it is more effective than ordinary conductive additives. The amount of the positive electrode active material 100 and the graphene compound 201 is reduced, and the electrical conductivity between the positive electrode active material 100 and the graphene compound 201 is improved. Therefore, the ratio of the granular positive electrode active material 100 in the active material layer 200 can be increased. This makes it possible to increase the discharge capacity of the power storage device.
[0120] Examples of binders include styrene-butadiene rubber (SBR) and styrene-isoprene. Acrylonitrile-styrene rubber, butadiene rubber, ethylene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, It is preferable to use a rubber material such as a propylene-diene copolymer. Fluorine rubber can be used.
[0121] As the binder, it is preferable to use, for example, a water-soluble polymer. As the molecule, for example, polysaccharides can be used. CMC, methyl cellulose, ethyl cellulose, hydroxypropyl cellulose Cellulose derivatives such as cellulose, diacetyl cellulose, regenerated cellulose, and starch These water-soluble polymers can be used in combination with the above-mentioned rubber materials. It is even better if there is a
[0122] Alternatively, the binder may be polystyrene, polymethyl acrylate, or polymethyl methacrylate. Polyvinyl chloride (Polymethyl methacrylate (PMMA)), Sodium polyacrylate, Polyvinyl chloride Polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, Polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene Polyethylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride Polyvinyl chloride (PVdF), polyacrylonitrile (PAN), ethylene propylene diene polymer It is preferable to use materials such as polyvinyl acetate and nitrocellulose.
[0123] The binder may be used in combination of two or more of the above.
[0124] For example, a material having a particularly excellent viscosity adjusting effect may be used in combination with other materials. For example, rubber materials have excellent adhesive strength and elasticity, but it is difficult to adjust the viscosity when mixed with a solvent. In such cases, for example, it is possible to mix the material with a particularly excellent viscosity adjusting effect. As a material having a particularly excellent viscosity adjusting effect, for example, a water-soluble polymer is preferably used. In addition, examples of water-soluble polymers that are particularly effective in adjusting viscosity include the aforementioned polysaccharides, such as calcium carbonate. Carboxymethylcellulose (CMC), methylcellulose, ethylcellulose, hydroxy Cellulose derivatives such as propyl cellulose, diacetyl cellulose, and regenerated cellulose For example, starch or starch can be used.
[0125] In addition, cellulose derivatives such as carboxymethyl cellulose are, for example, carboxymethyl The solubility of cellulose increases when it is converted into a salt such as sodium salt or ammonium salt. It is easy to exert its effect as a viscosity adjuster. The higher the solubility, the easier it is to make the electrode slurry. In the preparation of the electrode, the dispersibility of the electrode with the active material and other components can be improved. In this regard, the cellulose and cellulose derivatives used as the binder for the electrodes are as follows: These salts are also included.
[0126] Water-soluble polymers stabilize the viscosity by dissolving in water, and also serve as active materials and binders. Other materials to be combined, such as styrene butadiene rubber, are stable in aqueous solution. In addition, since it has a functional group, it is easy to stably adsorb on the surface of the active material. It is expected that cellulose derivatives such as carboxymethyl cellulose, for example, For example, many materials have functional groups such as hydroxyl groups and carboxyl groups. It is expected that the polymers will interact with each other and widely cover the surface of the active material.
[0127] When the binder that covers or contacts the surface of the active material forms a film, it is called a passive film. It is expected that the passive film will also play a role in preventing the decomposition of the electrolyte. It is a film with no or very low electrical conductivity, for example, on the surface of an active material. When a dynamic membrane is formed, it is possible to suppress the decomposition of the electrolyte at the battery reaction potential. In addition, the passive film suppresses electrical conductivity while allowing lithium ions to conduct. And even more desirable.
[0128] <Positive electrode current collector> The positive electrode current collector may be made of metals such as stainless steel, gold, platinum, aluminum, titanium, or the like. In addition, the material used for the positive electrode current collector can be an alloy of these materials, which has high electrical conductivity. It is preferable that the material does not dissolve at the potential of the positive electrode. Aluminum alloys containing elements such as indium and molybdenum that improve heat resistance are used. It can also be formed from a metal element that reacts with silicon to form a silicide. Metal elements that react with silicon to form silicide include zirconium, titanium, and Tantalum, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten , cobalt, nickel, etc. Current collectors are available in foil, plate (sheet), mesh, punched The current collector may be in the form of a metal, an expanded metal, or the like. It is advisable to use one with a thickness of 5 μm or more and 30 μm or less.
[0129] [Negative electrode] The negative electrode has a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer contains a conductive assistant and and a binder.
[0130] <Negative electrode active material> As the negative electrode active material, for example, an alloy-based material or a carbon-based material can be used.
[0131] As a negative electrode active material, it is possible to carry out charge / discharge reactions by alloying / de-alloying reactions with lithium. For example, silicon, tin, gallium, aluminum, and Rumanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. Materials containing at least one of these elements can be used. These elements have a large capacity compared to carbon. Silicon has a high theoretical capacity of 4200mAh / g. It is preferable to use silicon. Compounds containing these elements may also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V 2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3 Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, I nSb, SbSn, etc. Here, the charge / discharge reaction occurs due to alloying / dealloying reactions with lithium. Elements capable of undergoing a reaction and compounds containing such elements are sometimes called alloy materials. do.
[0132] In this specification, SiO refers to, for example, silicon monoxide. Alternatively, SiO x Here, it is preferable that x has a value close to 1. For example, x is 0 A value between 0.2 and 1.5 is preferred, and a value between 0.3 and 1.2 is more preferred.
[0133] Carbon-based materials include graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Carbon nanotubes, graphene, carbon black, etc. may be used. .
[0134] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include mesophase graphite. Carbon microbeads (MCMB), coke-based artificial graphite, pitch-based artificial graphite, etc. Here, as the artificial graphite, spherical graphite having a spherical shape can be used. For example, the MCMB may have a spherical shape, which is preferred. It is relatively easy to reduce the particle size, which may be preferable. Examples of the graphite include flake graphite and spherical natural graphite.
[0135] When lithium ions are inserted into graphite (when lithium-graphite intercalation compounds are formed), It has a low potential similar to that of lithium metal (0.05V to 0.3V vs. Li / L i + This allows the lithium-ion secondary battery to exhibit a high operating voltage. In addition, graphite has a relatively high capacitance per unit volume, a relatively small volume expansion, and is inexpensive. However, lithium ions are preferred because they have the advantage of being safer than metallic lithium.
[0136] In addition, titanium dioxide (TiO2) and lithium titanium oxide (Li4T i5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5) Oxides such as tungsten oxide (WO2) and molybdenum oxide (MoO2) can be used. can.
[0137] In addition, the negative electrode active material is a composite nitride of lithium and transition metals, which has a Li3N structure. Li 3-x M x N (M=Co, Ni, Cu) can be used. For example, Li 2.6 Co 0.4 N3 has a large charge / discharge capacity (900mAh / g, 1890mAh / cm 3 ) And preferable.
[0138] When a composite nitride of lithium and transition metals is used, the negative electrode active material contains lithium ions, The positive electrode active material is made of V2O5, Cr3O8, etc., which do not contain lithium ions. It is preferable that the positive electrode active material contains lithium ions. The lithium ions contained in the positive electrode active material are first removed to form the negative electrode active material. A complex nitride of lithium and a transition metal can be used.
[0139] In addition, a material that undergoes a conversion reaction can also be used as the negative electrode active material. For example, Lithium oxide (LiO), cobalt oxide (CoO), nickel oxide (NiO), iron oxide (FeO), etc. A transition metal oxide that does not form an alloy with the negative electrode active material may be used. The resulting materials include Fe2O3, CuO, Cu2O, RuO2, Cr2O3, etc. oxide, CoS 0.89 , NiS, CuS and other sulfides, Zn3N2, Cu3N, Ge3 Nitrides such as N4, phosphides such as NiP2, FeP2, CoP3, FeF3, BiF3, etc. It also occurs with fluoride.
[0140] The conductive assistant and binder that can be contained in the negative electrode active material layer are the same as those that can be contained in the positive electrode active material layer. The conductive additive and binder may be the same as those that can be used.
[0141] <Negative electrode current collector> The negative electrode current collector can be made of the same material as the positive electrode current collector. It is preferable to use a material that does not alloy with carrier ions such as lithium.
[0142] [Electrolyte] The electrolytic solution contains a solvent and an electrolyte. The solvent for the electrolytic solution is preferably an aprotic organic solvent. For example, ethylene carbonate (EC), propylene carbonate (PC), ethylene carbonate, chloroethylene carbonate, vinylene carbonate, gamma-butyrolactone lactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate ethyl propionate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1 ,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethylsulfur oxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran One of trihydrofuran, sulfolane, sultone, etc., or two or more of these Combinations and ratios may be used.
[0143] In addition, by using a polymer material that gels as a solvent for the electrolyte, safety against leakage, etc. is improved. The safety of the secondary battery is improved. In addition, the secondary battery can be made thinner and lighter. Representative examples of materials are silicone gel, acrylic gel, acrylonitrile gel, and polyethylene gel. Styrene oxide gel, polypropylene oxide gel, fluorine polymer gel, etc. There is.
[0144] In addition, a flame-retardant and non-volatile ionic liquid (room-temperature molten salt) is used as the solvent for the electrolyte. By using one or more batteries, the internal temperature of the storage device can be increased due to an internal short circuit or overcharging. Even if the battery is heated, it can prevent explosion or fire of the battery. Ionic liquids are made of cations and anions. The electrolyte solution contains an organic cation and an anion. Ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations, etc. Aliphatic onium cations such as imidazolium cations and pyridinium cations Aromatic cations are also used as anions in electrolytes. Anions, monovalent methide anions, fluorosulfonate anions, perfluoroalkyl Sulfonate anion, tetrafluoroborate anion, perfluoroalkylborate anion, hexafluorophosphate anion, or perfluoroalkyl phosphate anions, etc.
[0145] The electrolyte to be dissolved in the above solvent is, for example, LiPF6, LiClO4, Li AsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4 , Li2B 10 Cl 10 , Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO 3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2) 2. Lithium such as LiN(C4F9SO2)(CF3SO2) and LiN(C2F5SO2)2 Use one or more of these salts in any combination and ratio. can be done.
[0146] The electrolyte used in the electricity storage device is free of granular waste and elements other than the constituent elements of the electrolyte (hereinafter simply referred to as "inorganic It is preferable to use a highly purified electrolyte solution with a low content of ruthenium oxide (also called "pure substance"). Specifically, the weight ratio of impurities to the electrolyte is 1% or less, preferably 0.1% or less, more preferably It is preferably 0.01% or less.
[0147] In addition, vinylene carbonate, propane sultone (PS), and tert-butyl ether were used in the electrolyte. Benzene (TBB), Fluoroethylene Carbonate (FEC), LiBOB, and Squishi Additives such as dinitrile compounds such as diisopropylnitrile and adiponitrile may be added. The concentration of the agent may be, for example, 0.1 wt % to 5 wt % relative to the entire solvent.
[0148] Alternatively, a polymer gel electrolyte may be used in which a polymer is swollen with an electrolytic solution.
[0149] Examples of the polymer include polyalkylene oxides such as polyethylene oxide (PEO). Polymers with a fluororesin structure, PVDF, polyacrylonitrile, etc., and their combinations For example, a copolymer containing PVDF and hexafluoropropylene (H PVDF-HFP, a copolymer of PVDF and PVDF, can be used. The mer may have a porous shape.
[0150] In addition, instead of the electrolyte, solid electrolytes containing inorganic materials such as sulfides and oxides, and P A solid electrolyte containing a polymer material such as EO (polyethylene oxide) can be used. When a solid electrolyte is used, the installation of a separator or spacer becomes unnecessary. Since the entire pond can be solidified, there is no risk of leakage, and safety is improved dramatically.
[0151] [Separator] The secondary battery preferably has a separator. The separator may be, for example, a paper. Cellulose-containing fibers, nonwoven fabrics, glass fibers, ceramics, or nanofibers, including those containing cellulose, IRON (polyamide), VINYLON (polyvinyl alcohol fiber), polyester, acrylic The material used must be synthetic fibers such as olefin, polyolefin, and polyurethane. The separator is processed into an envelope shape and encases either the positive or negative electrode. It is preferable to arrange it as follows.
[0152] The separator may have a multi-layer structure. For example, the separator may be made of an organic material such as polypropylene or polyethylene. The material film is made of ceramic, fluorine, polyamide, or a combination of these. The ceramic material can be, for example, arsenic oxide. Aluminum particles, silicon oxide particles, etc. can be used. For example, PVDF, polytetrafluoroethylene, etc. can be used. Polyamide-based materials Examples of materials used include nylon and aramid (meta-aramid and para-aramid). It is possible.
[0153] Coating with ceramic materials improves oxidation resistance, making it ideal for separators during high-voltage charging and discharging. This suppresses the deterioration of the capacitor and improves the reliability of the secondary battery. By coating the electrode, the separator and the electrode are more easily adhered to each other, improving the output characteristics. Coating polyamide materials, especially aramid, improves heat resistance, which contributes to the safety of secondary batteries. This can improve safety.
[0154] For example, a mixture of aluminum oxide and aramid is coated on both sides of a polypropylene film. Alternatively, the surface of the polypropylene film that comes into contact with the positive electrode may be coated with aluminum oxide. Alternatively, the surface in contact with the negative electrode may be coated with a mixed material of rubber and aramid, and a fluorine-based material may be coated on the surface. .
[0155] By using a multi-layered separator, the safety of the secondary battery can be ensured even if the overall thickness of the separator is thin. Since the capacity per unit volume of the secondary battery can be increased, the capacity per unit volume of the secondary battery can be increased.
[0156] (Embodiment 3) In this embodiment, the shape of a secondary battery having the positive electrode active material 100 described in the previous embodiment is The material used in the secondary battery described in this embodiment is the same as that in the previous embodiment. The description of the form may be taken into consideration.
[0157] [Coin-type secondary battery] First, an example of a coin-type secondary battery will be described. Figure 4(A) shows a coin-type (single-layer flat type) FIG. 4(B) is a cross-sectional view of the secondary battery.
[0158] The coin-type secondary battery 300 has a positive electrode can 301 that also serves as a positive electrode terminal and a negative electrode can 302 that also serves as a negative electrode terminal. 302 is insulated and sealed by a gasket 303 made of polypropylene or the like. The positive electrode 304 is composed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector 305. The negative electrode 307 is formed by contacting a negative electrode current collector 308. The negative electrode active material layer 309 is formed by bonding the negative electrode active material layer 309 to the negative electrode.
[0159] The positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 are each an active material. The barrier layer need only be formed on one side.
[0160] The positive electrode can 301 and the negative electrode can 302 are made of nickel or aluminum, which is resistant to corrosion by the electrolyte. , titanium, or alloys of these with other metals (e.g. stainless steel In addition, nickel or aluminum can be used to prevent corrosion by the electrolyte. The positive electrode can 301 is for covering the positive electrode 304, and the negative electrode can 302 is for covering the negative electrode 304. 7 and electrically connected to each other.
[0161] The negative electrode 307, the positive electrode 304 and the separator 310 are impregnated with an electrolyte, as shown in FIG. As shown in FIG. 1, the positive electrode can 301 is placed downward, the positive electrode 304, the separator 310, the negative electrode 307, and the negative The positive electrode can 301 and the negative electrode can 302 are laminated in this order, and the positive electrode can 301 and the negative electrode can 302 are fixed with a gasket 303 interposed therebetween. Then, the laminate is pressed to manufacture a coin-type secondary battery 300.
[0162] By using the positive electrode active material described in the above embodiment for the positive electrode 304, it is possible to achieve high capacity cycling. The coin-type secondary battery 300 can be made to have excellent characteristics.
[0163] [Cylindrical secondary battery] Next, an example of a cylindrical secondary battery will be described with reference to FIG. As shown in FIG. 5(A), the positive electrode cap (battery cover) 601 is provided on the top surface, and the side and bottom surfaces are provided with The positive electrode cap 601 and the battery can (external can) 602 are disposed on the opposite sides of the positive electrode cap 601. ) 602 is insulated by a gasket (insulating packing) 610.
[0164] Fig. 5(B) is a schematic diagram showing a cross section of a cylindrical secondary battery. On the inside of 602, a strip-shaped positive electrode 604 and a negative electrode 606 are wound with a separator 605 sandwiched between them. Although not shown, the battery element is wound around a center pin. The battery can 602 is closed at one end and open at the other end. Metals such as nickel, aluminum, titanium, etc., which are resistant to corrosion by the electrolyte, or Alloys of these and other metals (eg, stainless steel, etc.) can be used. In order to prevent corrosion by the electrolyte, it is preferable to coat the material with nickel, aluminum, or the like. The battery element, in which the positive electrode, the negative electrode, and the separator are wound, is The battery is sandwiched between a pair of opposing insulating plates 608 and 609. The inside of the battery can 602 is filled with a non-aqueous electrolyte (not shown). The same as the in-type secondary battery can be used.
[0165] The positive and negative electrodes used in cylindrical secondary batteries are wound, so active material is formed on both sides of the current collector. A positive electrode terminal (positive electrode current collecting lead) 603 is connected to the positive electrode 604, and a negative A negative electrode terminal (negative electrode current collecting lead) 607 is connected to the positive electrode 606. The positive terminal 607 may be made of a metal material such as aluminum. 03 is resistance welded to the safety valve mechanism 612, and the negative terminal 607 is resistance welded to the bottom of the battery can 602. The safety valve mechanism 612 is a PTC (Positive Temperature Coefficient) The positive electrode cap 601 is electrically connected to the positive electrode cap 601 via a capacitance 611. The safety valve mechanism 612 is a mechanism for releasing the positive electrode cap 601 when the internal pressure of the battery increases beyond a predetermined threshold. The PTC element 611 cuts off the electrical connection between the positive electrode 604 and the positive electrode 604. It is a thermal resistor element whose resistance increases when the temperature rises, and the amount of current is limited by the increase in resistance. It prevents abnormal heat generation. The PTC element is made of barium titanate (BaTiO3) Semiconductor ceramics and the like can be used.
[0166] By using the positive electrode active material described in the above embodiment for the positive electrode 604, it is possible to achieve high capacity and cycle. This results in a cylindrical secondary battery 600 with excellent characteristics.
[0167] [Structural example of power storage device] Another structural example of the power storage device will be described with reference to FIGS.
[0168] 6(A) and 6(B) are diagrams showing the external appearance of the power storage device. The battery 900 and a secondary battery 913 are attached with a label 910. As shown in FIG. 6B, the power storage device has a terminal 951, a terminal 952, and an The antenna 914 and the antenna 915 .
[0169] The circuit board 900 includes a terminal 911 and a circuit 912. The terminal 911 is connected to a terminal 951. , a terminal 952, an antenna 914, an antenna 915, and a circuit 912. A plurality of terminals 911 are provided, and each of the plurality of terminals 911 is used as a control signal input terminal, a power supply terminal, etc. may also be used.
[0170] The circuit 912 may be provided on the back surface of the circuit board 900. The antenna 915 is not limited to a coil shape, but may be, for example, a wire shape or a plate shape. Planar antenna, aperture antenna, traveling wave antenna, EH antenna, magnetic field antenna, dielectric Alternatively, antenna 914 or antenna 915 may be used. The flat conductor may function as one of the conductors for electric field coupling. In other words, the annulus can be used as one of the two conductors of the capacitor. In this way, the electromagnetic field, the magnetic field, and the like can be detected by the antenna 914 or the antenna 915. Alternatively, power can be exchanged using an electric field.
[0171] The line width of antenna 914 is preferably larger than the line width of antenna 915. This allows the amount of power received by the antenna 914 to be increased.
[0172] The power storage device includes a layer 916 between the antenna 914 and the secondary battery 913 and between the antenna 915 and the secondary battery 913. The layer 916 has a function of shielding an electromagnetic field generated by the secondary battery 913, for example. The layer 916 may be made of, for example, a magnetic material.
[0173] The structure of the electricity storage device is not limited to that shown in FIG.
[0174] For example, as shown in Figs. 7(A-1) and 7(A-2), In the secondary battery 913 shown in FIG. FIG. 7(A-1) is an external view seen from one side of the pair of faces, and FIG. 7(A-2) is an external view seen from one side of the pair of faces. 6(A) and 6(B) are external views seen from the other side of the pair of surfaces. For the same parts as those of the power storage device shown in FIG. 6(A) and FIG. 6(B), the description of the power storage device shown in FIG. It can be used as needed.
[0175] As shown in FIG. 7(A-1), a layer 916 is sandwiched between one of a pair of surfaces of a secondary battery 913 to form an annular 7(A-2), a retainer 914 is provided on the other of the pair of surfaces of the secondary battery 913. The layer 917 is provided on the secondary battery 913, for example. The layer 917 has a function of preventing the influence of the electromagnetic field caused by the magnetic field. The sexual body can be used.
[0176] By adopting the above structure, the size of both the antenna 914 and the antenna 915 can be increased. It is possible.
[0177] Or, as shown in FIG. 7(B-1) and FIG. 7(B-2), A separate antenna may be provided on each of a pair of opposing surfaces of secondary battery 913. FIG. 7(B-1) is an external view seen from one side of the pair of faces, and FIG. 7(B-2) is 6(A) and 6(B) are external views seen from the other side of the pair of surfaces. Regarding the same parts as those of the power storage device shown in FIG. It can be used as appropriate.
[0178] As shown in FIG. 7(B-1), a layer 916 is sandwiched between one of a pair of surfaces of a secondary battery 913 to form an annular 7B-2, a secondary battery 91 An antenna 918 is provided on the other of the pair of surfaces of the substrate 3 with a layer 917 interposed therebetween. The antenna 918 is For example, the antenna 918 has a function of performing data communication with an external device. For example, an antenna having a shape applicable to antenna 914 and antenna 915 may be applied. As a method for communication between the power storage device and other devices via the antenna 918, NFC is used. It is possible to apply a response method that can be used between the power storage device and other devices, such as the above. Cut.
[0179] Alternatively, as shown in FIG. 8A, the secondary battery 913 shown in FIG. 6A and FIG. 6B may be A display device 920 may be provided. The display device 920 is electrically connected to the terminal 911 via the terminal 919. It is not necessary to provide the label 910 in the portion where the display device 920 is provided. Note that the same parts as those in the power storage device shown in FIG. 6(A) and FIG. 6(B) are The description of the power storage device in FIG. 6B can be used as appropriate.
[0180] The display device 920 displays, for example, an image indicating whether charging is in progress, an image indicating the amount of stored power, etc. The display device 920 may be, for example, an electronic paper, a liquid crystal display device, an electrophotographic display device, or the like. For example, an electroluminescence (EL) display device can be used. By using the par, the power consumption of the display device 920 can be reduced.
[0181] Alternatively, as shown in FIG. 8B, the sensor may be connected to the secondary battery 913 shown in FIG. 6A and FIG. 6B. The sensor 921 may be electrically connected to the terminal 911 via a terminal 922. Note that the same parts as those in the power storage device shown in FIG. 6(A) and FIG. 6(B) are The description of the power storage device in FIGS. 6A and 6B can be used as appropriate.
[0182] The sensor 921 may be, for example, a sensor for detecting displacement, position, speed, acceleration, angular velocity, number of rotations, distance, light, etc. , liquid, magnetic, temperature, chemical, sound, time, hardness, electric field, current, voltage, power, radiation, flow It is sufficient if the device has the function of measuring the amount, humidity, gradient, vibration, odor, or infrared rays. By providing the sensor 921, for example, data indicating the environment in which the power storage device is placed can be obtained. It is also possible to detect a signal (such as temperature) and store it in memory within the circuit 912.
[0183] Further, a structural example of the secondary battery 913 will be described with reference to FIGS.
[0184] A secondary battery 913 shown in FIG. 9A is provided with a terminal 951 and a terminal 952 inside a housing 930. The winding body 950 is impregnated with an electrolyte inside the housing 930. The terminal 952 is in contact with the housing 930, and the terminal 951 is in contact with the housing by using an insulating material or the like. 930. For convenience, the housing 930 is shown in FIG. However, in reality, the winding body 950 is covered by the housing 930, and the terminals 951 and 952 are The housing 930 is made of a metal material (e.g., aluminum). etc.) or resin materials can be used.
[0185] As shown in FIG. 9B, the housing 930 shown in FIG. 9A is formed from a plurality of materials. For example, the secondary battery 913 shown in FIG. The wound body 950 is disposed in the area surrounded by the housing 930a and the housing 930b. It is provided.
[0186] The housing 930a can be made of an insulating material such as an organic resin. By using a material such as organic resin on the surface on which the secondary battery 913 is formed, If the shielding of the electric field by the housing 930a is small, the shielding of the housing 930a can be suppressed. Antennas such as antenna 914 and antenna 915 may be provided inside the housing 930b. For example, a metal material can be used.
[0187] The structure of the wound body 950 is shown in FIG. The winding body 950 has a pole 932 and a separator 933. The negative electrode 931 and the positive electrode 932 are stacked on top of each other, and the laminated sheet is wound to form a wound body. The negative electrode 931, the positive electrode 932, and the separator 933 are laminated together. You can stack several of them.
[0188] The negative electrode 931 is connected to the terminal 911 shown in FIG. 6 via one of the terminals 951 and 952. The positive electrode 932 is connected to the terminal 911 shown in FIG. Connected.
[0189] By using the positive electrode active material described in the above embodiment for the positive electrode 932, the battery can be cycled with a high capacity. The secondary battery 913 can have excellent characteristics.
[0190] [Laminated secondary battery] Next, an example of a laminated secondary battery will be described with reference to FIGS. If the laminated secondary battery is made flexible, the flexible portion is at least If the secondary battery is mounted on an electronic device that also has a battery, the secondary battery can be bent according to the deformation of the electronic device. can.
[0191] A laminated secondary battery 980 will be described with reference to FIG. The battery 980 has a wound body 993 shown in FIG. 10, a positive electrode 995, and a separator 996. Similar to the wound body 950, a negative electrode 994 and a positive electrode 995 are stacked with a separator 996 interposed therebetween. The laminated sheet is then wound.
[0192] The number of layers of the negative electrode 994, the positive electrode 995, and the separator 996 is determined as required. The negative electrode 994 is connected to the lead electrode 997 and the lead The positive electrode 995 is connected to a negative electrode collector (not shown) via one of the lead electrodes 998. The other of the electrode 997 and the lead electrode 998 is connected to a positive electrode current collector (not shown).
[0193] As shown in FIG. 11B, a film 981 that serves as an exterior body and a film 98 having a recess are 2 are bonded together by thermocompression or the like to form a space in which the above-mentioned wound body 993 is housed. In this way, a secondary battery 980 can be manufactured as shown in FIG. 3 has a lead electrode 997 and a lead electrode 998, a film 981, and a recess The inside of the film 982 is impregnated with an electrolyte.
[0194] The film 981 and the film 982 having the recesses are made of a metal material such as aluminum. The film 981 and the film 982 having the recesses can be made of a resin material. If a resin material is used as the material, when an external force is applied, the film 981 and the recessed portion The film 982 having the electrode can be deformed to produce a secondary battery having flexibility. can be done.
[0195] In addition, although Fig. 11(B) and Fig. 11(C) show an example in which two films are used, A space is formed by folding one sheet of film, and the above-mentioned wound body 99 is inserted into the space. It may also accommodate 3.
[0196] By using the positive electrode active material described in the previous embodiment for the positive electrode 995, it is possible to achieve high capacity cycling. The secondary battery 980 can have excellent characteristics.
[0197] In addition, in FIG. 11, a secondary battery 9 having a wound body in a space formed by a film that serves as an exterior body is shown. We have explained the example of 80, but as shown in Figure 12, the shape is determined by the film that is the exterior body. The space defined by the positive electrode layer can be used as a secondary battery having a plurality of rectangular positive electrodes, separators, and negative electrodes. good.
[0198] The laminated secondary battery 500 shown in FIG. 12(A) includes a positive electrode current collector 501 and a positive electrode active material. A positive electrode 503 having a positive electrode active material layer 502, a negative electrode current collector 504 and a negative electrode active material layer 505. The battery includes a negative electrode 506, a separator 507, an electrolyte 508, and an exterior body 509. A separator 507 is provided between a positive electrode 503 and a negative electrode 506 provided in a body 509. The exterior body 509 is filled with an electrolyte 508. The electrolyte solution shown in the second embodiment can be used.
[0199] In the laminated secondary battery 500 shown in FIG. 12(A), a positive electrode current collector 501 and a negative electrode current collector The positive electrode current collector 504 also serves as a terminal for obtaining electrical contact with the outside. A part of the current collector 501 and the negative electrode current collector 504 is exposed to the outside from the exterior body 509. In addition, the positive electrode current collector 501 and the negative electrode current collector 504 may be arranged in a manner similar to that described above. Instead of exposing it to the outside, a lead electrode is used to connect the lead electrode to the positive electrode current collector 501 or the negative electrode The lead electrode may be exposed to the outside by ultrasonic bonding to the current collector 504 .
[0200] In the laminated secondary battery 500, the exterior body 509 is made of, for example, polyethylene, poly A film made of propylene, polycarbonate, ionomer, polyamide, etc. is coated with a A thin metal film with excellent flexibility, such as aluminum, stainless steel, copper, or nickel, is applied. On the metallic thin film, an insulating synthetic resin such as polyamide resin or polyester resin is applied as the outer surface of the exterior body. A laminate film having a three-layer structure with an oil film can be used.
[0201] An example of the cross-sectional structure of a laminated secondary battery 500 is shown in FIG. For simplicity, A) shows an example consisting of two current collectors, but in reality, it is composed of multiple electrode layers. It consists of:
[0202] In FIG. 12B, as an example, the number of electrode layers is 16. In FIG. 12B, the negative electrode current collector 504 has eight layers. The positive electrode current collector 501 has a structure of 8 layers, totaling 16 layers. The cross section of the extraction part is shown, and eight layers of negative electrode current collector 504 are ultrasonically bonded. The number of electrode layers is not limited to 16, and may be more or less. In addition, when the number of electrode layers is small, the secondary battery can have a larger capacity. In this case, a secondary battery can be made thin and has excellent flexibility.
[0203] An example of the external appearance of a laminated secondary battery 500 is shown in FIGS. 13 and 14. 3 and 14 show a positive electrode 503, a negative electrode 506, a separator 507, an outer casing 509, a positive electrode lead The positive electrode 510 and the negative electrode 511 are connected to each other.
[0204] FIG. 15A shows an external view of a positive electrode 503 and a negative electrode 506. The positive electrode 503 is connected to a positive electrode current collector 50 1, and the positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. 503 has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab region). 506 has a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. In addition, the negative electrode 506 has a region where the negative electrode current collector 504 is partially exposed, that is, a tab region. The area and shape of the tab regions of the positive electrode and the negative electrode are not limited to the example shown in FIG. I can't.
[0205] [Method of manufacturing laminated secondary battery] Here, an example of a method for producing a laminated secondary battery shown in FIG. 13 will be described with reference to FIG. This will be explained using (B) and (C).
[0206] First, the negative electrode 506, the separator 507, and the positive electrode 503 are laminated. The negative electrode 506, the separator 507, and the positive electrode 503 are shown. Next, the bonding of the tab regions of the positive electrode 503 and the bonding of the tabs of the positive electrode on the outermost surface are shown. The positive electrode lead electrode 510 is bonded to the region. For example, ultrasonic welding or the like may be used for bonding. Similarly, the bonding between the tab regions of the negative electrodes 506 and the bonding of the negative electrode leads to the tab region of the outermost negative electrode are preferably performed. Then, the metal layer 511 is bonded.
[0207] Next, the negative electrode 506 , the separator 507 and the positive electrode 503 are placed on the exterior body 509 .
[0208] Next, as shown in FIG. 15(C), the exterior body 509 is folded at the portion indicated by the dashed line. After that, the outer periphery of the exterior body 509 is bonded. For example, thermocompression bonding may be used for bonding. 509, so that the electrolyte 508 can be poured in later. An area that is not joined (hereinafter referred to as an inlet) is provided.
[0209] Next, the electrolyte 508 is introduced into the inside of the exterior body 509 through an inlet provided in the exterior body 509. The electrolyte 508 is preferably introduced under a reduced pressure or an inert gas atmosphere. Finally, the inlet is joined. In this way, a laminated secondary battery is produced. A secondary battery 500 can be fabricated.
[0210] By using the positive electrode active material described in the above embodiment for the positive electrode 503, it is possible to achieve high capacity and cycle. The secondary battery 500 can have excellent characteristics.
[0211] [Bendable secondary battery] Next, an example of a bendable secondary battery will be described with reference to FIGS. 16 and 17. .
[0212] FIG. 16(A) shows a schematic top view of a bendable battery 250. (B2) and (C) are cut along the lines C1-C2 and C3-C4 in FIG. 16(A), respectively. 2 is a schematic cross-sectional view taken along the line A1-A2. The positive electrode 211a and the negative electrode 211b are housed inside the battery 251. A lead 212a electrically connected to the negative electrode 211b and a lead 21 2b extends outside the exterior body 251. In addition, in the area surrounded by the exterior body 251, In addition to the electrode 211a and the negative electrode 211b, an electrolyte (not shown) is enclosed.
[0213] The positive electrode 211a and the negative electrode 211b of the battery 250 will be described with reference to FIG. FIG. 17(A) illustrates the stacking order of the positive electrode 211a, the negative electrode 211b, and the separator 214. FIG. 17(B) shows a perspective view of the positive electrode 211a and the negative electrode 211b, as well as a lead 2 12a and a lead 212b.
[0214] As shown in FIG. 17A, the battery 250 includes a plurality of rectangular positive electrodes 211a, a plurality of rectangular The positive electrode 211a and the negative electrode 211b are connected to the positive electrode 211a and the negative electrode 211b. Each of the positive electrodes 211a and 211b has a protruding tab portion and a portion other than the tab. A positive electrode active material layer is formed on the portion other than the tab, and the negative electrode 211b is formed on the portion other than the tab on one surface of the negative electrode 211b. A negative electrode active material layer is formed.
[0215] The surfaces of the positive electrode 211a on which the positive electrode active material layer is not formed and the surfaces of the negative electrode 211b on which the negative electrode active material layer is not formed are The positive electrode 211a and the negative electrode 211b are laminated so that the surfaces on which the porous layer is not formed are in contact with each other. will be done.
[0216] In addition, the surface on which the positive electrode active material layer of the positive electrode 211a is formed and the surface on which the negative electrode active material layer of the negative electrode 211b is formed are A separator 214 is provided between the formed surfaces. Separator 214 is shown in dotted lines.
[0217] As shown in FIG. 17B, the positive electrodes 211a and the leads 212a are connected to each other through a joint 215. The negative electrodes 211b and the leads 212b are electrically connected to each other at the joints 211a. Electrical connection is made at 15b.
[0218] Next, the exterior body 251 will be described with reference to FIGS. 16(B1), (B2), (C), and (D). do.
[0219] The exterior body 251 has a film-like shape and is arranged to sandwich the positive electrode 211a and the negative electrode 211b. The exterior body 251 is folded in two at the folded portion 261 and a pair of seal portions 2 The pair of sealing parts 262 are connected to the positive electrode 211a and the negative electrode 211b. The seal portion 26 is provided on either side of the electrode 211b and can also be called a side seal. 3 has a portion overlapping with the lead 212a and the lead 212b, and is also called a top seal. This can be done.
[0220] The exterior body 251 has a ridge line 271 and a valley line 272 at the portion overlapping the positive electrode 211a and the negative electrode 211b. It is preferable that the sealing portion 26 of the exterior body 251 has a corrugated shape in which the grooves 72 are arranged alternately. 2 and the seal portion 263 are preferably flat.
[0221] FIG. 16(B1) is a cross section cut at the portion overlapping with the ridge line 271, and FIG. 16(B2) is a cross section cut at the portion overlapping with the ridge line 271. The cross section is taken at the part overlapping with the valley line 272. 250 and 251 correspond to cross sections in the width direction of the positive electrode 211a and the negative electrode 211b.
[0222] Here, the distance between the end of the negative electrode 211b in the width direction and the seal portion 262 is defined as La. When the battery 250 is deformed, for example by bending, the positive electrode 211a and the negative electrode In this case, if the distance La is too short, the outer The exterior body 251 rubs strongly against the positive electrode 211a and the negative electrode 211b, and the exterior body 251 is damaged. In particular, if the metal film of the exterior body 251 is exposed, the metal film may become electrically Therefore, it is recommended to set the distance La as long as possible. On the other hand, if the distance La is too large, the volume of the battery 250 increases. Put away.
[0223] In addition, the greater the total thickness of the laminated positive electrode 211a and negative electrode 211b, the greater the It is preferable to increase the distance La between the end of b and the seal portion 262.
[0224] More specifically, a positive electrode 211a, a negative electrode 211b, and a separator (not shown) are stacked. When the total thickness of 214 is thickness t, the distance La is 0.8 to 3.0 times the thickness t. Preferably, the ratio is 0.9 to 2.5 times, more preferably 1.0 to 2.0 times. By setting the distance La in this range, the device is compact and has good resistance to bending. This makes it possible to realize a highly reliable battery.
[0225] In addition, when the distance between the pair of seal portions 262 is a distance Lb, the distance Lb is It is preferable that the width of the battery 250 is sufficiently larger than the width Wb of the battery 250. When the positive electrode 211a and the negative electrode 211b are deformed, the positive electrode 211a and the negative electrode 211b come into contact with the exterior body 251. Even if the positive electrode 211a and the negative electrode 211b are in contact with each other, a part of the positive electrode 211a and the negative electrode 211b can be shifted in the width direction. To effectively prevent the electrode 211a and the negative electrode 211b from rubbing against the exterior body 251. can be done.
[0226] For example, the difference between the distance Lb between the pair of seal portions 262 and the width Wb of the negative electrode 211b is 1.6 times or more and 6.0 times or less, preferably 1.8 times, the thickness t of the negative electrode 211a and the negative electrode 211b It is preferable that the ratio is 2.0 to 4.0 times. .
[0227] In other words, it is preferable that the distance Lb, the width Wb, and the thickness t satisfy the relationship of the following formula 1. It is nice.
[0228]
number
[0229] Here, a is 0.8 or more and 3.0 or less, preferably 0.9 or more and 2.5 or less, and more preferably is greater than or equal to 1.0 and less than or equal to 2.0.
[0230] FIG. 16C is a cross section including the lead 212a, showing the battery 250, the positive electrode 211a and As shown in FIG. 16(C), the bent portion 2 corresponds to a cross section of the negative electrode 211b in the longitudinal direction. In 61, the ends of the positive electrode 211a and the negative electrode 211b in the longitudinal direction and the exterior body 251 are It is preferable to have a space 273 therebetween.
[0231] FIG. 16(D) shows a schematic cross-sectional view of the battery 250 when bent. This corresponds to the cross section taken along line B1-B2 in FIG. 16(A).
[0232] When the battery 250 is bent, the part of the exterior body 251 located on the outside of the bend stretches, and the part located on the inside More specifically, the part located on the outside of the exterior body 251 is deformed so as to shrink. The outer casing 251 deforms so that the amplitude of the wave becomes smaller and the period of the wave becomes larger. The part located inside the ridge deforms so that the wave amplitude is large and the wave period is small. In this way, the deformation of the exterior body 251 reduces the load applied to the exterior body 251 due to bending. Since the stress is relieved, the material that constitutes the exterior body 251 does not need to expand or contract. As a result, the battery 250 can be bent with a small force without damaging the exterior body 251.
[0233] Furthermore, as shown in FIG. 16(D), when the battery 250 is bent, the positive electrode 211a and the negative electrode 21 At this time, the stacked positive electrodes 211a and negative electrodes 211b are shifted relative to each other. Since one end of 211b on the side of the seal portion 263 is fixed by the fixing member 217, The amount of deviation increases toward the positive electrode 21. The stress applied to the positive electrode 211a and the negative electrode 211b is relieved, and the positive electrode 211a and the negative electrode 211b themselves As a result, the positive electrode 211a and the negative electrode 211b do not need to expand and contract. The battery 250 can be bent.
[0234] In addition, a space 273 is provided between the ends of the positive electrode 211a and the negative electrode 211b and the exterior body 251. As a result, when the electrode is bent, the ends of the positive electrode 211a and the negative electrode 211b located on the inside are However, the electrode 252 can be relatively displaced without coming into contact with the exterior body 251.
[0235] The battery 250 illustrated in FIG. 16 and FIG. 17 has a casing that retains its shape even after repeated bending and straightening. The positive electrode 211a and the negative electrode 211b are unlikely to break, and the battery characteristics are unlikely to deteriorate. The positive electrode 211a of the battery 250 is made of the positive electrode active material described in the previous embodiment. By using this material, it is possible to produce a battery with higher capacity and better cycle characteristics.
[0236] (Embodiment 4) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on an electronic device will be described. do.
[0237] First, as described in part of the third embodiment, a bendable secondary battery is mounted on an electronic device. Examples are shown in Figures 18(A) to 18(G). For example, television equipment (also called television or television receiver), computers, Computer monitors, digital cameras, digital video cameras, digital photo frames, etc. mobile phones (also called mobile phones or mobile phone devices), portable game machines, portable information terminals, Examples include audio playback devices and large game machines such as pachinko machines.
[0238] In addition, the flexible secondary battery can be mounted on the inner or outer walls of houses or buildings, or on the inside or outside of automobiles. It is also possible to incorporate it along the curved surfaces of the interior or exterior of the vehicle.
[0239] FIG. 18A shows an example of a mobile phone. A mobile phone 7400 includes a housing 7401. In addition to the display unit 7402, operation buttons 7403, an external connection port 7404, The mobile phone 7400 is equipped with a speaker 7405, a microphone 7406, etc. The secondary battery 7407 is a secondary battery of one embodiment of the present invention. This makes it possible to provide a lightweight mobile phone with a long life.
[0240] FIG. 18B shows the mobile phone 7400 in a curved state. When the battery is deformed by applying an external force to the battery, the secondary battery installed inside the battery is released. The secondary battery 7407 is also bent. At this time, the state of the bent secondary battery 7407 is shown in FIG. The secondary battery 7407 is a thin storage battery. The secondary battery 7407 is in a bent state. The secondary battery 7407 is fixed in place by a resistor. The electrode is a gate electrode.
[0241] FIG. 18D shows an example of a bangle-type display device. The portable display device 7100 is The device includes a housing 7101 , a display unit 7102 , operation buttons 7103 , and a secondary battery 7104 . FIG. 18E shows the bent state of the secondary battery 7104. When the device is attached to the user's arm, the housing may deform and cause damage to part of the secondary battery 7104 or The total curvature changes. Note that the degree of curvature at any point on the curve is expressed as the radius of the corresponding circle. The value expressed is the radius of curvature, and the inverse of the radius of curvature is called the curvature. Within the range of 40 mm to 150 mm, a part of the main surface of the case or the secondary battery 7104 The radius of curvature of the main surface of the secondary battery 7104 is 40 mm or more and 150 mm or less. If the thickness is within the range of 1 mm or less, high reliability can be maintained. By using the secondary battery of one embodiment, a lightweight, long-life portable display device can be provided.
[0242] FIG. 18F shows an example of a wristwatch-type portable information terminal. The portable information terminal 7200 is , a housing 7201, a display unit 7202, a band 7203, a buckle 7204, and an operation button 72 05, input / output terminal 7206, etc.
[0243] The portable information terminal 7200 is capable of carrying out mobile telephone calls, e-mails, viewing and creating documents, playing music, and using the Internet. - It can run various applications such as internet communication and computer games. do.
[0244] The display unit 7202 has a curved display surface, and displays images along the curved display surface. The display portion 7202 is provided with a touch sensor, and can be used to input a touch signal to the screen using a finger or a stylus. For example, the icon 72 displayed on the display unit 7202 can be operated by touching it. You can launch the application by touching 07.
[0245] The operation button 7205 is used to set the time, turn the power on and off, and turn wireless communication on and off. It has various functions such as operation, silent mode activation and deactivation, power saving mode activation and deactivation, etc. For example, an operating system installed in the portable information terminal 7200 can The function of the operation button 7205 can also be freely set using the stem.
[0246] In addition, the mobile information terminal 7200 is capable of performing short-distance wireless communication according to a communication standard. For example, by communicating with a wireless headset, You can also make calls.
[0247] The portable information terminal 7200 also includes an input / output terminal 7206, and a connector for connecting to other information terminals. Data can be exchanged directly through the input / output terminal 7206. The charging operation can be performed by wireless power supply without going through the input / output terminal 7206. This is also possible.
[0248] A display portion 7202 of a portable information terminal 7200 includes a secondary battery of one embodiment of the present invention. By using the secondary battery of one embodiment of the present invention, a lightweight portable information terminal with a long life can be provided. For example, the secondary battery 7104 shown in FIG. 18E is curved inside the housing 7201. or may be incorporated in a bendable state inside the band 7203.
[0249] The portable information terminal 7200 preferably has a sensor. For example, a fingerprint sensor may be used as the sensor. Sensors for human body such as pulse sensors, body temperature sensors, touch sensors, pressure sensors, acceleration sensors It is preferable that the above-mentioned components are mounted on the vehicle.
[0250] FIG. 18G shows an example of a wristband-type display device. The display device 7300 includes a display unit 7 The display device 7300 includes a display 304 and a secondary battery of one embodiment of the present invention. The display unit 7304 may be equipped with a touch sensor, and may function as a portable information terminal. It is also possible.
[0251] The display surface of the display unit 7304 is curved, and the display can be performed along the curved display surface. In addition, the display device 7300 can display a display state by short-distance wireless communication according to a communication standard. The situation can be changed.
[0252] The display device 7300 also has an input / output terminal, and can directly connect to other information terminals via a connector. It is also possible to charge the device via the input / output terminals. The charging operation may be performed by wireless power supply without going through the input / output terminals.
[0253] By using the secondary battery of one embodiment of the present invention as the secondary battery included in the display device 7300, It is possible to provide a display device with a long life and low cost.
[0254] FIG. 1 shows an example in which the secondary battery having excellent cycle characteristics shown in the above embodiment is mounted on an electronic device. 18(H), FIG. 19 and FIG. 20.
[0255] By using the secondary battery of one embodiment of the present invention as a secondary battery in everyday electronic devices, the device can be lightweight and have a long life. For example, we can provide a wide range of products for daily electronic devices, such as electric toothbrushes, electric shavers, These include mobile beauty devices, and the secondary batteries for these products are designed to be easy for users to carry. Therefore, there is a demand for a stick-shaped secondary battery that is small, lightweight, and has a large capacity.
[0256] FIG. 18(H) is a perspective view of a device also called a tobacco-containing smoking device (electronic cigarette). In 18(H), the electronic cigarette 7500 is an atomizer 7501 that includes a heating element and an atomizer A secondary battery 7504 that supplies power to the myza, and a cart including a liquid supply bottle and sensors, etc. The secondary battery 7504 is composed of a ridge 7502. To enhance safety, the secondary battery 7504 is protected from overcharging and overcharging. A protection circuit for preventing discharge may be electrically connected to the secondary battery 7504. The secondary battery 7504 has an external terminal so that it can be connected to a charging device. The 504 is the tip when held, so the total length is short and the weight is light. Since the secondary battery of one embodiment of the present invention has a high capacity and good cycle characteristics, We offer the 7500 electronic cigarette, which is small and lightweight and can be used for long periods of time. Can be provided.
[0257] Next, FIG. 19(A) and FIG. 19(B) show an example of a foldable tablet terminal. The tablet terminal 9600 shown in FIG. 19(A) and FIG. 19(B) includes a housing 9630. a, housing 9630b, a movable part 9640 connecting the housing 9630a and the housing 9630b, Part 9631, display mode changeover switch 9626, power switch 9627, power saving mode The display has a mode changeover switch 9625, a fastener 9629, and an operation switch 9628. The display unit 9631 can be made of a flexible panel, making it possible to produce a tablet with a wider display area. FIG. 19(A) shows a tablet terminal 9600 in an open state. 19(B) shows the tablet terminal 9600 in a closed state.
[0258] The tablet terminal 9600 also includes a battery storage device inside the housing 9630a and the housing 9630b. The power storage unit 9635 is connected to the housing 9630a through the movable portion 9640. It is located across 9630b.
[0259] A part of the display unit 9631 can be used as a touch panel area, and the user can operate the displayed operation keys. You can enter data by touching the screen. You can also switch the keyboard display on the touch panel. By touching the area where the replacement button is displayed with your finger or a stylus, the display 9631 Keyboard buttons can be displayed.
[0260] A display mode changeover switch 9626 is used to change the display orientation between portrait and landscape. You can switch between black and white and color display. The touch 9625 detects when in use by an optical sensor built into the tablet terminal 9600. The brightness of the display can be optimized according to the amount of external light. In addition to optical sensors, other sensors such as gyros and acceleration sensors that detect tilt are also available. The device may be built-in.
[0261] FIG. 19(B) shows the tablet terminal in a closed state. The tablet terminal includes a housing 9630 and a solar cell 96 33, a charge / discharge control circuit 9634 including a DCDC converter 9636. A secondary battery according to one embodiment of the present invention is used as the body 9635.
[0262] In addition, since the tablet terminal 9600 can be folded in two, when not in use, the housing 9630a and The housing 9630b can be folded so that the housing 9630a and the housing 9630b overlap each other. Since the display portion 9631 can be protected, the durability of the tablet terminal 9600 can be improved. In addition, the power storage unit 9635 using the secondary battery of one embodiment of the present invention has a high capacity and a good cycle life. The tablet terminal 9600 has a long-term usable lifespan due to its thermal characteristics. We can provide it.
[0263] In addition, the tablet terminals shown in Figs. 19(A) and 19(B) can be used in various Functions that display information (still images, videos, text images, etc.), calendars, dates, or times A function to display information on the display unit, and a function to input or edit information displayed on the display unit. It has input functions, functions to control processing by various software (programs), etc. It is possible.
[0264] The solar cell 9633 attached to the surface of the tablet device supplies power to the touch panel, The solar cell 9633 can be provided to a display unit, a video signal processor, or the like. The structure can be provided on one or both sides of the power storage unit 9630, and can efficiently charge the power storage unit 9635. It can be said that it is completed.
[0265] The configuration and operation of the charge / discharge control circuit 9634 shown in FIG. A block diagram is shown in FIG. 19(C) and will be described. FIG. 19(C) shows a solar cell 9633 and a power storage unit 963 5, DC-DC converter 9636, converter 9637, switches SW1 to SW3, table The display unit 9631 is shown, which includes a storage battery 9635, a DC-DC converter 9636, and a The inverter 9637 and the switches SW1 to SW3 are connected to the charge / discharge control circuit 96 shown in FIG. This corresponds to 34.
[0266] First, an example of operation in which power is generated by the solar cell 9633 using external light will be described. The power generated by the solar cell is converted to a voltage for charging the storage battery 9635 by the DCDC controller. The voltage is increased or decreased by a inverter 9636. When power from the 9633 is used, switch SW1 is turned on and the converter 9637 The voltage is increased or decreased to a voltage required for the display unit 9631. When not displaying the battery status, turn SW1 off and SW2 on to charge the battery 9635. The configuration may be such that the power supply is electrically connected to the power source.
[0267] The solar cell 9633 is shown as an example of a power generating means, but is not limited thereto. Storage of electricity by other power generation means such as piezoelectric elements and thermoelectric conversion elements For example, the device may be configured to transmit and receive power wirelessly (contactlessly). It is also possible to combine it with a non-contact power transmission module that charges the battery by using a contactless power transmission method, or other charging methods. This is also fine.
[0268] FIG. 20 shows another example of electronic equipment. In FIG. 20, a display device 8000 according to one embodiment of the present invention is 8 is an example of an electronic device using a secondary battery 8004 according to an embodiment. 8000 corresponds to a display device for receiving TV broadcasts, and includes a housing 8001, a display unit 8002, and a speaker unit. The secondary battery 8004 according to one embodiment of the present invention includes a housing 8003 and a secondary battery 8004. The display device 8000 is provided inside a body 8001. The display device 8000 receives power from a commercial power source. Alternatively, the power stored in the secondary battery 8004 can be used. Even when power cannot be supplied from a commercial power source due to a power outage or the like, the present invention according to one embodiment of the present invention By using the secondary battery 8004 as an uninterruptible power supply, the display device 8000 can be used. do.
[0269] The display unit 8002 may be a liquid crystal display device, an emitting device having light emitting elements such as organic EL elements in each pixel, or the like. Device, electrophoretic display device, DMD (Digital Micromirror Devi ce), PDP (Plasma Display Panel), FED (Field A semiconductor display device such as a 3D Emission Display can be used.
[0270] In addition, display devices are used for TV broadcast reception, personal computers, advertising displays, etc. , all display devices for displaying information are included.
[0271] In FIG. 20, a stationary lighting device 8100 includes a secondary battery 81 according to one embodiment of the present invention. 8101, a light source 8102, and a light source 8103 are used. In FIG. 20, the secondary battery 8103 is disposed in the housing 81. 8102 is installed inside a ceiling 8104. However, the secondary battery 8103 may be provided inside the housing 8101. The device 8100 can receive power from a commercial power source, or store power in a secondary battery 8103. Therefore, when the power supply from the commercial power source is cut off due to a power outage, Even when the electricity cannot be received, the secondary battery 8103 according to one embodiment of the present invention is used as an uninterruptible power source. This enables the lighting device 8100 to be used.
[0272] In addition, FIG. 20 illustrates a lighting device 8100 that is installed on a ceiling 8104. However, in the secondary battery according to one embodiment of the present invention, other than the ceiling 8104, for example, the side wall 8105, the floor 8106, 106, the window 8107, etc., can be used as a fixed lighting device, or a tabletop lighting device. The present invention can also be used in lighting devices of this type.
[0273] In addition, the light source 8102 may be an artificial light source that artificially obtains light using electricity. Specifically, incandescent lamps, fluorescent lamps and other discharge lamps, light emitting diodes (LEDs) and organic electroluminescence (EL) elements The element is an example of the artificial light source.
[0274] In FIG. 20, an air conditioner having an indoor unit 8200 and an outdoor unit 8204 is as follows: 8 is an example of an electronic device using a secondary battery 8203 according to one embodiment of the present invention. The device 8200 includes a housing 8201, an air outlet 8202, a secondary battery 8203, and the like. 8 illustrates an example in which the secondary battery 8203 is provided in the indoor unit 8200. The battery 8203 may be provided in the outdoor unit 8204. A secondary battery 8203 may be provided in both the power source 8202 and the power source 8204. The power supply can be provided from a commercial power source, or the power stored in the secondary battery 8203 can be used. In particular, a secondary battery 82 is provided in both the indoor unit 8200 and the outdoor unit 8204. If 03 is installed, when power cannot be supplied from the commercial power source due to a power outage, etc. In addition, by using the secondary battery 8203 according to one embodiment of the present invention as an uninterruptible power supply, The conditioner can be used.
[0275] In Figure 20, a separate type air conditioner consisting of an indoor unit and an outdoor unit is shown. As an example, an all-in-one air conditioner that has both indoor and outdoor unit functions in a single housing. The secondary battery according to one embodiment of the present invention can also be used for the conditioner.
[0276] In FIG. 20, an electric refrigerator-freezer 8300 includes a secondary battery 8304 according to one embodiment of the present invention. Specifically, an electric refrigerator-freezer 8300 includes a housing 8301, a refrigerator It has a storage compartment door 8302, a freezer compartment door 8303, a secondary battery 8304, etc. A secondary battery 8304 is provided inside the housing 8301. The electric refrigerator-freezer 8300 is It can receive power from a commercial power source, or use the power stored in the secondary battery 8304. Therefore, when power cannot be supplied from commercial power sources due to a power outage, etc. However, by using the secondary battery 8304 according to one embodiment of the present invention as an uninterruptible power supply, It will be possible to use the 8300 freezer refrigerator.
[0277] In addition, during periods when electronic devices are not in use, especially during periods when the total amount of power that can be supplied by commercial power suppliers is low, During times when the ratio of electricity actually used (called the electricity usage rate) is low, By storing power in the battery, it is possible to prevent high power usage outside of the above time periods. For example, in the case of the electric refrigerator-freezer 8300, when the temperature is low, the refrigerator compartment door 830 2. During the night when the freezer door 8303 is not opened or closed, the secondary battery 8304 stores electricity. Then, as the temperature rises, the refrigerator door 8302 and the freezer door 8303 are opened and closed. During the daytime, when the vehicle is turned on, the secondary battery 8304 is used as an auxiliary power source, and the daytime power usage rate is can be kept low.
[0278] In addition to the electronic devices described above, the secondary battery of one embodiment of the present invention can be mounted on various electronic devices. According to one embodiment of the present invention, the cycle characteristics of the secondary battery can be improved. According to this aspect, a high-capacity secondary battery can be obtained, and therefore the secondary battery itself can be made small and lightweight. Therefore, the secondary battery according to one embodiment of the present invention can be By incorporating this in electronic devices, the electronic devices can have a longer life and become lighter in weight. The embodiment can be implemented in appropriate combination with other embodiments.
[0279] (Embodiment 5) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on a vehicle will be described.
[0280] When a secondary battery is installed in a vehicle, it becomes a hybrid vehicle (HEV), electric vehicle (EV), or powertrain. This will make it possible to realize next-generation clean energy vehicles such as plug-in hybrid vehicles (PHEVs). .
[0281] FIG. 21 illustrates an example of a vehicle using a secondary battery according to one embodiment of the present invention. The automobile 8400 shown in FIG. 1 is an electric automobile that uses an electric motor as a power source for driving. Alternatively, an electric motor and an engine can be selected as the power source for driving. By using one embodiment of the present invention, the cruising distance can be extended. In addition, the automobile 8400 has a secondary battery. If many small cylindrical secondary batteries, as shown in Figure 5, are arranged on the floor of the vehicle, In addition, a battery pack made up of multiple secondary batteries as shown in FIG. 14 can be attached to the floor of the vehicle. The secondary battery may be installed not only to drive the electric motor 8406 but also to power the headlights. It can supply power to a light emitting device such as a light source 8401 or a room light (not shown).
[0282] In addition, the secondary battery is used for the display of the speedometer, tachometer, etc. of the automobile 8400. The secondary battery can supply power to the navigation device of the automobile 8400. The present invention can provide power to semiconductor devices such as power distribution systems.
[0283] The automobile 8500 shown in FIG. 21(B) is a secondary battery that is plugged in. The device can be charged by receiving power from an external charging facility using a contactless charging method or other methods. FIG. 21(B) shows a diagram of a charging device 8021 installed on the ground and a charging station 8022 installed on a vehicle 8500. The secondary battery 8024 is shown being charged via a cable 8022. For charging methods and connector specifications, please refer to the designated specifications of CHAdeMO (registered trademark) or Combo. The charging device 8021 is a charging station installed in a commercial facility. For example, plug-in technology can be used to The secondary battery 8024 installed in the automobile 8500 can be charged by the power supply. Charging is performed by converting AC power to DC power via a conversion device such as an ACDC converter. It is possible.
[0284] Although not shown, a power receiving device is mounted on the vehicle and receives power from a ground power transmitting device in a non-contact manner. In this non-contact power supply method, a power transmission device is installed on the road or exterior wall. By incorporating this technology, charging can be done not only when the vehicle is stopped but also while it is moving. Using this method, electric power may be transmitted between vehicles. A solar battery may be installed to charge the secondary battery when the vehicle is stopped or running. The power can be supplied using an electromagnetic induction method or a magnetic resonance method.
[0285] FIG 21C shows an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. The scooter 8600 shown in (C) has a secondary battery 8602, side mirrors 8601, and a turn signal. The secondary battery 8602 can supply electricity to the direction indicator light 8603. can.
[0286] In addition, the scooter 8600 shown in FIG. 21(C) has a secondary battery 860 in the storage space under the seat 8604. 2 can be stored. The secondary battery 8602 can be stored in the under-seat storage 8604 even if it is small. The secondary battery 8602 can be removed and stored in the under-seat storage 8604. When charging, the secondary battery 8602 is brought indoors, charged, and stored before driving. Just do that.
[0287] According to one aspect of the present invention, the cycle characteristics of the secondary battery are improved, and the capacity of the secondary battery is increased. Therefore, the secondary battery itself can be made smaller and lighter. If the body can be made smaller and lighter, it will contribute to reducing the weight of the vehicle, which will improve the driving range. In addition, the secondary battery installed in the vehicle can also be used as a power supply source for purposes other than the vehicle. In this case, for example, it is possible to avoid using commercial power sources during peak power demand periods. If we can avoid using commercial power sources during peak power demand periods, we can save energy and This can contribute to reducing carbon dioxide emissions. In addition, if the cycle characteristics are good, Since the secondary battery can be used for a long period of time, the amount of rare metals used, including cobalt, can be reduced. It is possible.
[0288] This embodiment mode can be implemented in appropriate combination with other embodiment modes. EXAMPLES
[0289] In this example, secondary batteries using positive electrode active materials having different coating layers were produced and their characteristics were compared. The results are shown below.
[0290] <Preparation of positive electrode active material> Positive electrode active materials, Sample 1 to Sample 5, were prepared. The preparation method for each sample was as follows: I passed.
[0291] <Sample 1> Sample 1 has lithium cobalt oxide inside and aluminum and magnesium on the surface. In order to obtain a positive electrode active material having a coating layer containing magnesium and fluorine, The lithium particles are coated with an aluminum-containing coating layer by the sol-gel method, and then heated. Made.
[0292] Lithium cobalt oxide particles containing magnesium and fluorine are manufactured by Nippon Kagaku Kogyo Co., Ltd. (product name: ;C-20F) was used.
[0293] Add 0.0348g of tri-i-propoxyaluminum to 20ml of 2-propanol. The aluminum was dissolved in 2-propanol solution of tri-i-propoxyaluminum. 5 g of lithium cobalt oxide particles containing magnesium and fluorine were added.
[0294] The mixture was stirred with a magnetic stirrer for 4 hours at 25°C and 90% RH. This treatment resulted in hydration of the H2O in the atmosphere and tri-i-propoxyaluminum. Decomposition and polycondensation reactions are carried out to produce lithium cobalt oxide particles containing magnesium and fluorine. An aluminum-containing layer was formed on the surface of the substrate.
[0295] The mixed solution after the above treatment was filtered, and the residue was collected. (No.4) was used.
[0296] The collected residue was dried in vacuum at 70° C. for 1 hour.
[0297] The dried powder was heated to 800°C (heating rate: 200°C / hour) for 2 hours. The experiment was carried out in a dry air atmosphere.
[0298] The heated powder was cooled and crushed by sieving. The sieve used had an opening size of 53 μm.
[0299] The particles after the crushing treatment were used as the positive electrode active material of Sample 1.
[0300] <Sample 2> Sample 2 is a comparative example, and has lithium cobalt oxide inside and magnesium on the surface. In order to obtain a positive electrode active material having a coating layer containing magnesium and fluorine, lithium cobalt oxide having magnesium and fluorine is used. It was produced by heating lithium particles.
[0301] The lithium cobalt oxide particles containing magnesium and fluorine were manufactured by Nippon Kagaku Kogyo Co., Ltd. (product name: C -20F) was used.
[0302] The lithium cobalt oxide particles containing magnesium and fluorine were heated for 800 The heating was performed at 200° C. (heating rate: 200° C. / hour), with a holding time of 2 hours, in an oxygen atmosphere.
[0303] The heated powder was cooled and sieved through a 53 μm mesh sieve to obtain the positive electrode active material of sample 2. It was of high quality.
[0304] <Sample 3> Sample 3 is a comparative example of lithium cobalt oxide containing magnesium and fluorine. In order to obtain a positive electrode active material in which magnesium is not sufficiently segregated in the surface layer, magnesium is The lithium cobalt oxide particles having fluorine were used as they were without heating.
[0305] The lithium cobalt oxide particles containing magnesium and fluorine were manufactured by Nippon Kagaku Kogyo Co., Ltd. (product name: C -20F) was used.
[0306] <Sample 4> Sample 4 is a comparative example having lithium cobalt oxide inside and aluminum on the surface. In order to obtain a positive electrode active material having a coating layer containing magnesium, lithium cobalt oxide having no magnesium is used. The aluminum-containing coating layer was formed on aluminum particles by the sol-gel method, and then heated. .
[0307] As magnesium-free lithium cobalt oxide particles, Nippon Kagaku Kogyo Co., Ltd. (product name: C- This is because no magnesium was detected by XPS and the fluorine content was about 1 atomic percent. The lithium cobalt oxide particles are produced.
[0308] The lithium cobalt oxide particles were treated with the sol-gel method to form aluminium oxide. A coating layer containing ruthenium was formed, heated, dried, and sieved. This was the positive electrode active material of Sample 4. The substance was
[0309] <Sample 5> Sample 5 is a comparative example in which magnesium is used as a positive electrode active material without a coating layer. Lithium cobalt oxide particles not containing the catalyst were used as is without heating.
[0310] As magnesium-free lithium cobalt oxide particles, Nippon Kagaku Kogyo Co., Ltd. (product name: C- 10N) was used.
[0311] The conditions for Samples 1 to 5 are shown in Table 1.
[0312] [Table 1]
[0313] <Cycle characteristics> Using the positive electrode active materials of Samples 1 to 5 prepared above, CR2032 type ( A coin-type secondary battery (diameter 20 mm, height 3.2 mm) was fabricated and its cycle characteristics were evaluated. .
[0314] The positive electrode is made of the positive electrode active material (LiCoO2) of Samples 1 to 5 and acetylene black. LiCoO2:AB:PVDF=9 The slurry mixed at a weight ratio of 5:2.5:2.5 was applied to an aluminum foil current collector. The following was used.
[0315] Lithium metal was used as the counter electrode.
[0316] The electrolyte used in the electrolytic solution is 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte contains ethylene carbonate (EC) and diethyl carbonate (DEC). C:DEC=3:7 (volume ratio) was mixed and vinylene carbonate (VC) was added to it. The material was added at 100% by weight.
[0317] The positive electrode can and the negative electrode can were made of stainless steel (SUS).
[0318] The measurement temperature for the cycle characteristic test was 25°C. Charging was performed at a current density of 68 The current density was then set at 1.4mA / g, with a constant current of 0.5mA / g and an upper limit voltage of 4.6V. The battery was charged at a constant voltage up to 1000 V. The battery was discharged at a constant voltage of 68.5 mA / g per unit weight of active material. The current was set at a minimum voltage of 2.5V.
[0319] 22(A) and 22(B) show secondary battery samples using the positive electrode active materials of Samples 1 to 5. Graphs showing the cycle characteristics of the battery are shown. Figure 22(A) shows the energy density when charged to 4.6 V, FIG. 22(B) is a graph showing the energy density maintenance rate when the battery is charged to 4.6 V. The energy density is the product of the discharge capacity and the average discharge voltage. The density peak top was taken as 100%.
[0320] As is clear from Fig. 22(A) and Fig. 22(B), the lithium cobalt oxide without a coating layer Compared with sample 5, which is made of aluminum, the positive electrode active material having a coating layer containing aluminum was Sample 4, which was made of the same material, showed slightly better cycle characteristics.
[0321] In addition, sample 2, which is lithium cobalt oxide particle having magnesium and fluorine, and sample In the comparison of sample 3, sample 2, which was heated, showed a higher solubility than sample 3, which was not heated. The cycle characteristics were also significantly improved. This is because magnesium is converted to lithium cobalt oxide by heating. This is thought to be the effect of segregation at the surface layer of the aluminum particles.
[0322] In addition, lithium cobalt oxide particles containing magnesium and fluorine were coated with a coating containing aluminum. Sample 1, which is a positive electrode active material having a coating layer formed thereon, exhibited extremely good cycle characteristics. These are sample 2, in which magnesium is segregated in the surface layer, and sample 3, in which the coating layer contains aluminum. The properties were superior to those of Sample 4, which was formed using aluminum and magnesium. By providing a coating layer having aluminum, it is possible to obtain a coating layer having magnesium. It is clear that the cycle characteristics can be improved compared to the case where only the coating layer is provided. I did. EXAMPLES
[0323] In this embodiment, lithium cobalt oxide particles having a coating layer containing aluminum and magnesium are Various analyses were conducted to clarify the characteristics of the children.
[0324] <xps> Samples 1, 2, and 3 of Example 1 were subjected to XPS analysis from the surface. In addition, the particles of Sample 1 in Example 1 were sampled after the sol-gel treatment and drying, but before heating. The results are shown in Table 2. Some percentages have been rounded off to the nearest 1%, so the total may not add up to 100%.
[0325] [Table 2]
[0326] In addition, using the results in Table 2, lithium, aluminum, cobalt, magnesium, oxygen, Table 3 shows the atomic ratio calculated assuming the total amount of fluorine to be 100 atomic %.
[0327] [Table 3]
[0328] XPS analysis can quantitatively analyze the surface of the positive electrode active material from about 5 nm. As shown in the above, in the case of Sample 1 and Sample 2, which are the positive electrode active materials that were heated, The atomic ratio of magnesium was increased more than that of sample 6 and sample 3, which were not subjected to the treatment. In other words, it was clear that heating caused magnesium to segregate in a region about 5 nm from the surface. It became clear.
[0329] In addition, Sample 1 and Sample 6 were prepared by forming a coating layer having aluminum by the sol-gel method. So, sample 1, which was heated, has more aluminum than sample 6, which was not heated. The atomic ratio of the ruthenium was small. Therefore, by heating, the ruthenium was removed from the surface in a region about 5 nm deep. It was presumed that aluminum had diffused.
[0330] Therefore, in the case of sample 1, which has a coating layer containing aluminum and magnesium, There is a lot of magnesium in the area, and aluminum is present in a deeper area than magnesium. It was inferred that this was the case.
[0331] <stem-fft> Next, the results of STEM observation and FFT analysis of sample 1 are shown in Figure 23. and shown in FIG.
[0332] 23(A) to 23(C) are bright field ST images of a cross section near the surface of the positive electrode active material of Sample 1. In FIG. 23(C), the surface layer of the positive electrode active material particle is filled with what is assumed to be magnesium. It can be seen that there are elements that are observed to be brighter than others. As far as could be observed, it was also observed that the crystal orientation was roughly consistent from the inside to the surface. .
[0333] FIG. 24(A-1) is a HAADF-STEM image of a cross section near the surface of the positive electrode active material of Sample 1. The FFT (Fast Fourier Transform) image of the area shown by FFT1 in FIG. 24(A-2). Some of the bright spots in the FFT image of Fig. 24(A-2) are shown in Fig. 24(A-3). We have decided to call them A, B, C, and O as shown.
[0334] For the bright spots in the FFT image of the area shown in FFT1, the actual measured values are OA, d=0.2 5 nm, OB was d=0.16 nm, and OC was d=0.26 nm. Also, ∠AOB=3 7°, ∠BOC=36°, ∠AOC=73°.
[0335] This is the ICDD (International Centre for Diffra Magnesium oxide (MgO) data in the I CDD45-0945), and data for cobalt oxide (CoO) (ICDD48-17 19) is close to the distance and angle obtained from
[0336] In the case of magnesium oxide, OA(1-11) has d = 0.24 nm, and OB(0-22) has d =0.15nm, OC(-1-11) is d=0.24nm, ∠AOB=35°, ∠BOC =35°, ∠AOC=71°.
[0337] In the case of cobalt oxide, OA(1-11) has d = 0.25 nm, and OB(0-22) has d =0.15nm, OC(-1-11) is d=0.25nm, ∠AOB=35°, ∠BOC =35°, ∠AOC=71°.
[0338] Therefore, the region of about 2 nm from the surface of the positive electrode active material particle shown in FFT1 is composed of rock salt type crystals. It was found that the FF region has a crystal structure and is an image of the
[0011] incident light. The area marked T1 has magnesium oxide or cobalt oxide, or It was inferred that the material contained both ruthenium and cobalt oxide.
[0339] FIG. 24(B-1) shows the HAADF- of the cross section near the surface of the same positive electrode active material as FIG. 24(A-1). The STEM image is the FFT image of the area indicated by FFT2 in Fig. 24(B-1). A part of the bright spots in the FFT image of Figure 24(B-2) is shown in Figure 24(B-3). We decided to call them A, B, C, and O.
[0340] For the bright spots in the FFT image of the area shown in FFT2, the actual measured values are OA and d=0.5 1 nm, OB was d=0.21 nm, and OC was d=0.25 nm. Also, ∠AOB=5 5°, ∠BOC=24°, ∠AOC=79°.
[0341] This is based on the data for lithium cobalt oxide (LiCoO2) in the ICDD database ( ICDD50-0653), and LiAl 0.2 Co 0.8 data of O2 (ICDD8 9-0912) are close to the distances and angles obtained therefrom.
[0342] In the case of lithium cobalt oxide (LiCoO2), OA(003) has d = 0.47 nm, OB (104) has d = 0.20 nm, OC(101) has d = 0.24 nm, ∠AOB = 55° , ∠BOC = 25°, and ∠AOC = 80°.
[0343] LiAl 0.2 Co 0.8 In the case of O2, OA(003) has d = 0.47 nm, OB(10 4) has d = 0.20 nm, OC(101) has d = 0.24 nm, ∠AOB = 55°, ∠B OC = 25°, and ∠AOC = 80°.
[0344] Therefore, the region from 3 nm deeper to about 6 nm from the surface of the cathode active material shown by FFT2 is a region having the same layered rock salt-type crystal structure as that of lithium cobalt oxide and LiAl 0.2 Co 0.8 O2, and it was revealed to be an image of [0-10] incidence.
[0345] <STEM-EDX (Element Mapping, Line Analysis)> Next, regarding the results of the EDX analysis of Sample 1, they are shown in FIGS. 25 and 26 .
[0346] FIG. 25 shows the STEM-EDX analysis results of a cross section near the surface of the cathode active material of Sample 1. FIG. 25(A-1) is a HAADF-STEM image, FIG. 25(A-2) is a cobalt element mapping, FIG. 25(B-1) is an aluminum element mapping, and FIG. 25(B-2) is a magnesium Figure 25(C) is the elemental mapping of uranium, and Figure 25(D) is the elemental mapping of fluorine.
[0347] As shown in FIG. 25(B-1), aluminum is present in a region of about 10 nm from the surface of the positive electrode active material. As shown in Figure 25(B-2), magnesium It was observed that the particles were segregated in a region of about 3 nm from the surface of the positive electrode active material. As shown in Fig. 5(C), almost no fluorine was detected near the surface, which is due to the EDX analysis. This was thought to be because fluorine, a light element, was difficult to detect.
[0348] Figure 26 shows the results of STEM-EDX line analysis of a cross section near the surface of the positive electrode active material of sample 1. Figure 26(A) is a HAADF-STEM image. The area surrounded by the white line in Figure 26(A) The graph showing the results of EDX analysis in the direction of the white arrow is shown in Figure 26(B). FIG. 26(C) is a graph showing a part of FIG. 26(B) enlarged. However, almost no fluorine was detected.
[0349] As shown in FIG. 26(C), magnesium and aluminum were present near the surface of the positive electrode active material of sample 1. The distribution of magnesium is closer to the surface than the distribution of aluminum. It was also found that the magnesium peak was more prominent than the aluminum peak. It was also found that cobalt and oxygen exist from the outermost surface of the positive electrode active material particles. It was presumed to exist.
[0350] From the results of the above XPS and EDX analyses, it is understood that Sample 1 is a first embodiment of the present invention. The first region is lithium cobalt oxide, the second region is lithium, and the third region is aluminum. a positive region having magnesium and oxygen as a third region; It was confirmed that the electrode active material was a part of the second region and the third region in sample 1. It was revealed that some of them overlapped.
[0351] In addition, in the graph of FIG. 26(B), the amount of oxygen detected is stable at a distance of 11 nm or more. The average amount of oxygen detected in this stable region is O ave Calculate the average value O ave 50% of Value of 0.5O ave The distance x of the measurement point showing the closest measurement value to the particle of the positive electrode active material is It was assumed to be the outermost surface.
[0352] In this embodiment, the average amount of oxygen detected in the range of 11 nm to 40 nm is ave The measurement point that showed the closest measurement value to 388.5, which is 50% of 777, was 777. The x-axis is the distance of 9.5 nm. Therefore, in this embodiment, It was estimated that the distance of 9.5 nm was the outermost surface of the positive electrode active material particle.
[0353] If the surface of the positive electrode active material particle is 9.5 nm, the magnesium peak is The aluminum peak was 2.3 nm from the outermost surface.
[0354] From the results of the above-mentioned Examples 1 and 2, it is possible to confirm that the first region 101 and the The second region 102 is made of lithium and aluminum. The third region 103 includes magnesium and oxygen. It has been shown that the positive electrode active material has excellent cycle characteristics when used in secondary batteries. It became so. [Explanation of symbols]
[0355] 100 Cathode active material 101 First Area 102 Second Area 103 The Third Region 104 The Fourth Region 200 Active material layer 201 Graphene Compounds 211a positive electrode 211b negative electrode 212a Lead 212b Lead 214 Separator 215a Joint 215b Joint 217 Fixing member 250 batteries 251 Exterior body 261 Bending part 262 Seal part 263 Seal Part 271 Ridgeline 272 Valley Line 273 Space 300 Secondary battery 301 Positive electrode can 302 Anode can 303 Gasket 304 Positive electrode 305 Positive electrode current collector 306 Positive electrode active material layer 307 Negative electrode 308 Negative electrode current collector 309 Negative electrode active material layer 310 Separator 500 secondary battery 501 Positive electrode current collector 502 Positive electrode active material layer 503 Positive electrode 504 Negative electrode current collector 505 Negative electrode active material layer 506 negative electrode 507 Separator 508 Electrolyte 509 Exterior body 510 Positive lead electrode 511 Negative lead electrode 600 Secondary battery 601 Positive electrode cap 602 Battery Can 603 Positive terminal 604 Positive electrode 605 Separator 606 negative electrode 607 Negative terminal 608 Insulating plate 609 Insulating plate 611 PTC element 612 Safety valve mechanism 900 Circuit Board 910 Label 911 Terminal 912 Circuit 913 Secondary battery 914 Antenna 915 Antenna 916 layers 917 layers 918 Antenna 919 Terminal 920 Display device 921 Sensor 922 Terminal 930 Case 930a Case 930b Case 931 negative electrode 932 Positive electrode 933 Separator 950 Wound body 951 Terminal 952 Terminal 980 Secondary battery 981 Film 982 Film 993 Wound body 994 negative electrode 995 positive electrode 996 Separator 997 Lead Electrode 998 Lead Electrode 7100 Portable display devices 7101 Case 7102 Display section 7103 Operation button 7104 Secondary battery 7200 Portable Information Terminal 7201 Case 7202 Display section 7203 Band 7204 Buckle 7205 Operation button 7206 Input / output terminal 7207 Icon 7300 display device 7304 Display section 7400 Mobile Phone 7401 Case 7402 Display section 7403 Operation button 7404 External connection port 7405 Speaker 7406 Mike 7407 Secondary battery 7409 Current collector 7500 Electronic Cigarettes 7501 Atomizer 7502 Cartridge 7504 Secondary battery 8000 display device 8001 Case 8002 Display section 8003 Speaker section 8004 Secondary battery 8021 Charging device 8022 Cable 8024 Secondary battery 8100 Lighting equipment 8101 Case 8102 Light source 8103 Secondary battery 8104 Ceiling 8105 Side wall 8106 Bed 8107 Window 8200 indoor unit 8201 Case 8202 Ventilator 8203 Secondary battery 8204 Outdoor unit 8300 Electric refrigerator-freezer 8301 Case 8302 Refrigerator door 8303 Freezer door 8304 Secondary battery 8400 Automobiles 8401 Headlight 8406 Electric Motor 8500 Automobiles 8600 Scooter 8601 Side mirror 8602 Secondary battery 8603 Turn signal light 8604 Under-seat storage 9600 Tablet PC 9625 Switch 9626 Switch 9627 Power Switch 9628 Operation Switch 9629 Fastener 9630 Case 9630a Case 9630b Case 9631 Display section 9633 Solar Cells 9634 Charge / discharge control circuit 9635 Electric storage unit 9636 DC-DC Converter 9637 Converter 9640 Moving parts < / xps>
Claims
1. A positive electrode active material, The positive electrode active material has a first region, a second region, and a third region, the first region is present inside the positive electrode active material, the second region covers at least a portion of the first region; the third region covers at least a portion of the second region; the first region comprises lithium, a transition metal, and oxygen; the second region comprises lithium, aluminum, the transition metal, and oxygen; The third region is a positive electrode active material having magnesium and oxygen.
2. In claim 1, The third region is a positive electrode active material having fluorine.
3. In claim 1 or 2, The third region is a positive electrode active material having the transition metal.
4. In any one of claims 1 to 3, the first region and the second region have a layered rock salt type crystal structure, The third region is a positive electrode active material having a rock salt type crystal structure.
5. In any one of claims 1 to 4, The positive electrode active material, wherein the transition metal is cobalt.
6. A positive electrode active material, The positive electrode active material includes lithium, aluminum, a transition metal, magnesium, oxygen, and fluorine, The total amount of lithium, aluminum, the transition metal, magnesium, oxygen, and fluorine measured from the surface of the positive electrode active material by X-ray photoelectron spectroscopy is taken as 100 atomic %, Measured from the surface of the positive electrode active material by X-ray photoelectron spectroscopy, The aluminum concentration is 0.1 atomic % or more and 10 atomic % or less, The magnesium concentration is 5 atomic % or more and 20 atomic % or less, A positive electrode active material having a fluorine concentration of 3.5 atomic % or more and 14 atomic % or less.
7. A positive electrode having the positive electrode active material according to any one of claims 1 to 6; A secondary battery having a negative electrode, an electrolyte, and an outer casing.
8. dissolving an aluminum alkoxide in an alcohol; mixing particles having lithium, a transition metal, magnesium, oxygen, and fluorine with an alcohol solution of aluminum alkoxide in which the aluminum alkoxide is dissolved in the alcohol; a step of stirring a mixture of the alcohol solution of the aluminum alkoxide and the particles having lithium, a transition metal, magnesium, oxygen, and fluorine in an atmosphere containing water vapor; recovering a precipitate from the mixture; heating the recovered precipitate in an oxygen-containing atmosphere at 500° C. to 1200° C. for a holding time of 50 hours or less; The method for producing a positive electrode active material comprising the steps of:
Citation Information
Patent Citations
Positive active material for lithium secondary battery
JP2001291518A
Positive electrode active material for lithium secondary battery
JP2003217572A
Positive electrode material for nonaqueous secondary batteries, manufacturing method thereof, positive electrode mixture layer for nonaqueous secondary batteries arranged by use of positive electrode material for nonaqueous secondary batteries, positive electrode for nonaqueous secondary batteries, and nonaqueous secondary battery
JP2015069958A
Lithium secondary battery
JP1996236114A
Positive electrode active material for lithium secondary battery and its manufacturing method
JP2002124262A